Composite graphite material and preparation method thereof, negative electrode sheet, secondary battery, battery module, battery pack, and electric device
Patent Information
- Application Number
- JP2023530727
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-09-15
- Filing Date
- 2022-05-18
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2042-05-18
AI Technical Summary
【0044】 本願に係る二次電池は、高いエネルギー密度を有するという前提で、さらに大幅に向上された急速充電性能及び低温出力性能を有することができる。本願に係る電池モジュール、電池パック及び電気装置は、本願が提供する二次電池を含むため、少なくとも前記二次電池と同様な利点を有する。
Smart Images

Figure 0007626571000004 
Figure 0007626571000005 
Figure 0007626571000006
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED PATENT APPLICATIONS This application claims priority to Chinese Patent Application No. 202111079771.0, filed on September 15, 2021, entitled "Composite graphite material and its preparation method, negative electrode sheet, secondary battery," which is incorporated herein by reference in its entirety.
[0002] The present application relates to the field of battery technology, in particular to a composite graphite material and its preparation method, a negative electrode sheet, a secondary battery, a battery module, a battery pack and an electric device. [Background technology]
[0003] Secondary batteries are charged and discharged by the reciprocating insertion and removal of active ions between the positive and negative electrodes, and have outstanding characteristics such as high energy density, long cycle life, no pollution, and no memory effect. Therefore, as a clean energy source, secondary batteries are gradually being used in large equipment fields such as electronic products and electric vehicles to meet the sustainable development strategy of the environment and energy. However, compared with the fast and timely refueling of traditional fuel vehicles, electric vehicles are generally charged at a small rate, which often requires a long charging time, which brings range anxiety to consumers and limits the rapid spread of electric vehicles. Summary of the Invention [Problem to be solved by the invention]
[0004] The present application aims to provide a composite graphite material having significantly improved fast charging performance and low-temperature output performance under the premise of providing a secondary battery with high energy density, a preparation method thereof, a negative electrode sheet, a secondary battery, a battery module, a battery pack, and an electric device. [Means for solving the problem]
[0005] A first aspect of the present application provides a composite graphite material including bulk particles, which are secondary particles formed by agglomeration of two or more primary particles, and a coating layer located on at least a part of the surface of the bulk particles, wherein the bulk particles include artificial graphite, the coating layer includes amorphous carbon, and the composite graphite material has an air oxidation temperature T0 of 630° C. to 730° C. The air oxidation temperature T0 is a temperature corresponding to an intersection of two tangents to two points corresponding to 500° C. and the T1 temperature, respectively, on a thermogravimetric curve of the composite graphite material, and the T1 temperature is a peak top temperature of a maximum area peak on a differential thermogravimetric curve of the composite graphite material, and the thermogravimetric curve and the differential thermogravimetric curve are obtained by thermogravimetric analysis performed under conditions of a sample mass of 10±0.05 mg, air as a purge gas, a gas flow rate of 60 mL / min, a heating rate of 5° C. / min, and a measurement temperature range of 35° C. to 950° C.
[0006] The air oxidation temperature T0 of the composite graphite material can accurately represent the temperature at which the weight loss due to air oxidation of the composite graphite material begins, and can therefore accurately reflect the number of end faces and defects of the composite graphite material. The air oxidation temperature T0 of the composite graphite material is 630℃-730℃, and at this time, the number of end faces and defects contained in the composite graphite material is moderate, the composite graphite material has good active ion and electron transport performance, the charge exchange speed of the active ions and electrons on the surface of the composite graphite material is relatively fast, and the active ion solid-phase transport ability in the composite graphite material is relatively high, so that the secondary battery has greatly improved fast charging performance and low-temperature output performance under the premise of having high energy density.
[0007] In any embodiment of the present application, the air oxidation temperature T0 of the composite graphite material is 660° C. to 710° C. When the air oxidation temperature T0 of the composite graphite material is within an appropriate range, the composite graphite material can have an appropriate number of end faces and defects, and the transport performance of active ions and electrons can be improved, and the rapid charging performance and low-temperature output performance of the secondary battery can be improved.
[0008] In any embodiment of the present application, the composite graphite material further comprises a dynamic carbon material.
[0009] In any embodiment of the present application, the dynamic carbon material is located at at least a portion of the interface between primary particles in the bulk particle.
[0010] In any embodiment of the present application, the dynamic carbon material is located in a coating layer.
[0011] In any embodiment of the present application, the dynamic carbon material is located in both the coating layer and at least a portion of the interface between the primary particles in the bulk particle.
[0012] In any embodiment of the present application, the dynamic carbon material raw material is one or more selected from hard carbon, fine expanded graphite, expanded graphite, and graphene, and the interlayer distance d of the (002) crystal plane of the dynamic carbon material raw material is 002 ≧0.3358 nm.
[0013] Optionally, the interlayer distance d of the (002) crystal plane of the dynamic carbon material raw material 002 is 0.3359nm to 0.3366nm.
[0014] When the dynamic carbon material obtained from the dynamic carbon material raw material is uniformly distributed in the bulk particles and / or coating layer of the composite graphite material, it is favorable for the rapid insertion and desorption of active ions, and can improve the transport performance of active ions and electrons, and can further improve the fast charging performance and low-temperature output performance of the secondary battery, without causing a loss of energy density of the secondary battery.
[0015] In any embodiment of the present application, based on the total mass of the composite graphite material, the mass percent content of the dynamic carbon material is 1% to 30%. Optionally, the mass percent content of the dynamic carbon material is 8% to 15%. When the mass percent content of the dynamic carbon material is within a suitable range, under the premise that the composite graphite material has a high gram capacity, it can have a relatively high active ion solid-phase transport ability and a relatively high charge exchange rate between active ions and electrons.
[0016] In any embodiment of the present application, the interlayer distance d of the (002) crystal plane of the composite graphite material 002 is 0.3355 nm to 0.3364 nm. Optionally, the interlayer distance d of the (002) crystal plane of the composite graphite material is 002 The interlayer distance d of the composite graphite material is relatively high. 002 When the active ion solid phase transport ability is improved, the rapid charging performance and low temperature output performance of the secondary battery can be improved.
[0017] In any embodiment of the present application, the composite graphite material has a volume average particle diameter Dv50 of 8.5 μm to 14.5 μm. Optionally, the composite graphite material has a volume average particle diameter Dv50 of 10 μm to 12 μm. When the volume average particle diameter Dv50 of the composite graphite material is within an appropriate range, the composite graphite material has better active ion and electron transport performance and fast charging performance, and the composite graphite material can have a relatively high powder compaction density.
[0018] In any embodiment of the present application, the volume average particle diameter Dv50 of the bulk particles is 7.5 μm to 13.5 μm. Optionally, the volume average particle diameter Dv50 of the bulk particles is 9.0 μm to 11.5 μm. When the volume average particle diameter Dv50 of the bulk particles of the composite graphite material is within a suitable range, the composite graphite material can have a higher gram capacity under the premise that it has better active ion and electron transport performance.
[0019] In any embodiment of the present application, the ratio of the volume average particle diameter Dv50 of the primary particles to the volume average particle diameter Dv50 of the secondary particles formed therefrom is 0.45 to 0.75. Optionally, the ratio of the volume average particle diameter Dv50 of the primary particles to the volume average particle diameter Dv50 of the secondary particles formed therefrom is 0.55 to 0.65. When the ratio is within an appropriate range, the bulk particles of the composite graphite material have a relatively good degree of secondary particle, which can improve the transport performance of active ions and electrons of the composite graphite material and provide relatively high structural stability.
[0020] In any embodiment of the present application, the weight percent content of amorphous carbon in the coating layer is 1% to 8% based on the total weight of the composite graphite material. Optionally, the weight percent content of amorphous carbon in the coating layer is 2% to 5%. When the content of amorphous carbon is within an appropriate range, the composite graphite material can have a high gram capacity and a relatively high active ion solid-phase transport ability.
[0021] In any embodiment of the present application, the composite graphite material has a powder compaction density of 1.45 g / cm at a force of 20,000 N. 3 ~1.75g / cm 3 Optionally, the powder compaction density of the composite graphite material at a force of 20,000 N is 1.55 g / cm 3 ~1.65g / cm 3 When the powder compaction density of the composite graphite material is within a suitable range, the negative electrode film layer has a relatively high compaction density, and the secondary battery can have a relatively high energy density. In addition, the composite graphite material has a high ability to maintain the pore structure of the negative electrode film layer during cycling, and the negative electrode sheet has better electrolyte infiltration, which also contributes to improving the cycle performance of the secondary battery.
[0022] The second aspect of the present application provides a method for preparing a composite graphite material, comprising the steps of: S10: providing coke powder or coke powder to which a dynamic carbon material raw powder has been added, and graphitizing the coke powder or the coke powder to which the dynamic carbon material raw powder has been added to obtain bulk particles, the bulk particles being secondary particles formed by agglomeration of two or more primary particles, and the bulk particles including artificial graphite; and S20: mixing the bulk particles with an organic carbon source, or mixing the bulk particles with an organic carbon source and the dynamic carbon material raw powder, and carbonizing the bulk particles to form a coating layer including amorphous carbon on at least a part of the surface of the bulk particles, thereby obtaining the composite graphite material. The dynamic carbon material raw powder is added to at least one of steps S10 and S20, and the dynamic carbon material raw material is one or more selected from hard carbon, fine expanded graphite, expanded graphite, and graphene, and the interlayer distance d of the dynamic carbon material raw material (002) crystal plane is 0.01 to 0.01 mm. 002 ≧0.3358 nm.
[0023] The air oxidation temperature T0 of the obtained composite graphite material is 630°C to 730°C, the air oxidation temperature T0 is the temperature corresponding to the intersection of two tangents to two points corresponding to 500°C and the T1 temperature, respectively, on the thermogravimetric curve of the composite graphite material, and the T1 temperature is the peak top temperature of the maximum area peak on the differential thermogravimetric curve of the composite graphite material, and the thermogravimetric curve and the differential thermogravimetric curve are obtained by thermogravimetric analysis performed under conditions of a sample mass of 10±0.05 mg, air as a purge gas, a gas flow rate of 60 mL / min, a heating rate of 5°C / min, and a measurement temperature range of 35°C to 950°C.
[0024] The method for preparing the composite graphite material according to the present application is simple to operate, low cost, and suitable for large-scale industrial production. The method according to the present application can obtain a composite graphite material with a suitable content of edge faces and defects, and the secondary battery can have significantly improved fast charging performance and low-temperature output performance under the premise of having a high energy density.
[0025] In any embodiment of the present application, the interlayer distance d of the (002) crystal plane of the dynamic carbon material raw material002 is 0.3359nm to 0.3366nm.
[0026] In any embodiment of the present application, based on the total mass of the obtained composite graphite material, the total mass percentage content of the dynamic carbon material raw powder added in steps S10 and S20 is 1% to 30%. Optionally, the total mass percentage content of the dynamic carbon material raw powder added in steps S10 and S20 is 8% to 15%.
[0027] In any embodiment of the present application, the volume average particle diameter Dv50 of the coke powder is 6 μm to 12 μm. Optionally, the volume average particle diameter Dv50 of the coke powder is 8 μm to 10 μm.
[0028] In any embodiment of the present application, the dynamic carbon material raw material powder has a volume average particle diameter Dv50 of 3 μm to 12 μm. Optionally, the dynamic carbon material raw material powder has a volume average particle diameter Dv50 of 4 μm to 9 μm.
[0029] In any embodiment of the present application, the ratio of the volume average particle diameter Dv50 of the coke powder to the volume average particle diameter Dv50 of the dynamic carbon material raw powder is 1.05 to 1.75. Optionally, the ratio of the volume average particle diameter Dv50 of the coke powder to the volume average particle diameter Dv50 of the dynamic carbon material raw powder is 1.2 to 1.5. When the ratio of the volume average particle diameter Dv50 of the coke powder to the volume average particle diameter Dv50 of the dynamic carbon material raw powder is within an appropriate range, the bulk particles of the composite graphite material can have a relatively good degree of secondary particles.
[0030] In any embodiment of the present application, the method further includes the steps of adding a binder to S10, mixing the binder with coke powder to granulate, and graphitizing to obtain bulk particles, or mixing the binder with coke powder to which the dynamic carbon material raw material powder is added to granulate, and graphitizing to obtain bulk particles. The addition of a binder is favorable for making the bulk particles of the composite graphite material have a relatively good degree of secondary particles, improving the transport performance of active ions and electrons of the composite graphite material, and making the composite graphite material have a relatively high structural stability.
[0031] In any embodiment of the present application, based on the total mass of the obtained composite graphite material, the mass percent content of the binder is 3% to 12%. Optionally, the mass percent content of the binder is 5% to 8%. When the content of the binder is within a suitable range, excessive particle aggregation can be avoided, and the bulk particles of the composite graphite material can have a relatively good degree of secondary particles.
[0032] In any embodiment of the present application, the binder is selected from asphalt.
[0033] In any embodiment of the present application, the particles obtained by granulation have a volume average particle diameter Dv50 of 8 μm to 14 μm. Optionally, the particles obtained by granulation have a volume average particle diameter Dv50 of 9.5 μm to 12 μm.
[0034] In any embodiment of the present application, in S20, the organic carbon source is one or more selected from coal asphalt, petroleum asphalt, phenolic resin, and coconut shell. Optionally, the organic carbon source is selected from petroleum asphalt.
[0035] In any embodiment of the present application, the amount of the organic carbon source added is such that the mass percent content of amorphous carbon obtained by carbonizing the organic carbon source is 1% to 8% based on the total mass of the obtained composite graphite material. Optionally, the amount of the organic carbon source added is such that the mass percent content of amorphous carbon obtained by carbonizing the organic carbon source is 2% to 5%. When the amount of the organic carbon source added is within an appropriate range, the composite graphite material can have a high gram capacity and a relatively high active ion solid phase transport ability.
[0036] A third aspect of the present application provides a negative electrode sheet including a negative electrode current collector and a negative electrode film layer provided on at least one surface of the negative electrode current collector, the negative electrode film layer including the composite graphite material of the first aspect of the present application or the composite graphite material prepared by the method of the second aspect of the present application.
[0037] In any embodiment of the present application, the negative electrode film layer further contains an additive, the additive being one or more selected from hard carbon, fine expanded graphite, expanded graphite, and graphene, and the interlayer distance d of the additive (002) crystal plane is 002 ≧0.3358nm. These additives have relatively good active ion and electron transport properties, and can greatly improve the fast charging performance and low temperature output performance under the premise of making the secondary battery have high energy density.
[0038] In any embodiment of the present application, the interlayer distance d of the additive (002) crystal plane 002 is 0.3359nm to 0.3366nm.
[0039] In any embodiment of the present application, based on the total mass of the negative electrode membrane layer, the mass percent content of the additive is 1% to 20%. Optionally, the mass percent content of the additive is 3% to 8%. When the mass percent content of the additive is within a suitable range, the secondary battery can have significantly improved fast charging performance and low temperature output performance under the premise of having high energy density. In addition, when the mass percent content of the additive is within a suitable range, the ability of maintaining the pore structure of the negative electrode membrane layer during the cycle process is higher, the electrolyte infiltration of the negative electrode sheet is better, and the secondary battery has better cycle performance.
[0040] A fourth aspect of the present application provides a secondary battery including the negative electrode sheet according to the third aspect of the present application.
[0041] A fifth aspect of the present application provides a battery module including the secondary battery of the fourth aspect of the present application.
[0042] A sixth aspect of the present application provides a battery pack including one of the secondary battery according to the fourth aspect of the present application and the battery module according to the fifth aspect.
[0043] A seventh aspect of the present application provides an electric device including at least one of the secondary battery according to the fourth aspect, the battery module according to the fifth aspect, and the battery pack according to the sixth aspect of the present application. Effect of the Invention
[0044] The secondary battery according to the present application may have significantly improved fast charging performance and low temperature output performance on the premise of having a high energy density. The battery module, battery pack and electric device according to the present application include the secondary battery provided by the present application, and therefore have at least the same advantages as the secondary battery. [Brief description of the drawings]
[0045] In order to more clearly explain the technical solutions of the embodiments of the present application, the following briefly introduces drawings necessary for the embodiments of the present application. However, the drawings described below are only a part of the embodiments of the present application, and it is obvious to those skilled in the art that they can obtain other drawings based on the drawings without paying creative labor.
[0046] [Figure 1] FIG. 1 is a schematic diagram of one embodiment of a composite graphite material according to the present application. [Diagram 2] FIG. 2 is a schematic diagram of another embodiment of a composite graphite material according to the present application. [Diagram 3] FIG. 2 is a schematic diagram of another embodiment of a composite graphite material according to the present application. [Figure 4] 1 is a schematic diagram of one embodiment of a secondary battery according to the present application. [Diagram 5] 1 is an exploded schematic view of one embodiment of a secondary battery according to the present application. [Figure 6] 1 is a schematic diagram of one embodiment of a battery module according to the present application. [Figure 7] 1 is a schematic diagram of one embodiment of a battery pack according to the present application. [Figure 8] FIG. 5 is an exploded view of FIG. [Figure 9] FIG. 1 is a schematic diagram of one embodiment of an electrical device that uses a secondary battery according to the present application as a power source. [Figure 10] FIG. 2 is a diagram showing thermogravimetric curves and differential thermogravimetric curves of the composite graphite materials of Example 3 and Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0047] Hereinafter, with appropriate reference to the drawings, embodiments specifically disclosing the composite graphite material and its preparation method, negative electrode sheet, secondary battery, battery module, battery pack, and electric device according to the present application will be described in detail. However, unnecessary detailed explanations may be omitted. For example, detailed explanations of already well-known matters and redundant explanations of substantially the same configurations may be omitted. This is to avoid the following explanation from becoming unnecessarily redundant and to facilitate understanding by those skilled in the art. Note that the drawings and the following explanations are provided to enable those skilled in the art to fully understand the present disclosure, and are not intended to limit the subject matter described in the claims.
[0048] The "ranges" disclosed herein are defined in the form of lower and upper limits, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower and upper limits define the boundaries of the particular range. Such defined ranges may or may not include the end values, and may be arbitrarily combined, i.e., any lower limit may be combined with any other upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a particular parameter, the ranges of 60-110 and 80-120 are also expected to be understood. Also, if the minimum range values listed are 1 and 2, and the maximum range values listed are 3, 4, and 5, then ranges such as 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5 are all expected. In this specification, unless otherwise stated, the numerical range "a-b" represents an abbreviation for any combination of real numbers between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for combinations of these numbers. Also, when a parameter is expressed as an integer ≧2, this is equivalent to disclosing that the parameter is an integer, for example, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0049] Unless otherwise specified, all the embodiments and optional embodiments in the present application can be combined with each other to form a new technical solution.
[0050] Unless otherwise specified, all technical features and optional technical features of the present application can be combined with each other to form a novel technical solution.
[0051] Unless otherwise stated, all steps in the present application may be performed in sequence or randomly, preferably in sequence. For example, the method includes steps (a) and (b), which means that the method performs steps (a) and (b) in sequence, or performs steps (b) and (a) in sequence. For example, the method mentioned above may further include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), may include steps (a), (c) and (b), may include steps (c), (a) and (b), etc.
[0052] Unless otherwise specified, the terms "comprise" and "contain" referred to herein mean to be open-ended and may be closed-ended. For example, the terms "comprise" and "contain" mean that other components not listed may also be included or contained, and may only include or contain the listed components.
[0053] Unless otherwise specified, in the present invention, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B." Specifically, any of the following conditions also satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist), A is false (or does not exist) and B is true (or exists), or A and B are true (or exist).
[0054] In this specification, "fine expanded graphite" means graphite having a bulk volume change before and after expansion (i.e., expansion ratio) of 80 to 200, and "expanded graphite" means graphite having a bulk volume change before and after expansion (i.e., expansion ratio) > 200.
[0055] In this specification, the term "coke raw material" refers to a component that can be processed to obtain "coke", i.e., a raw material for producing coke. "Coke" refers to a product obtained by subjecting a coke raw material to a coke treatment, "coke powder" and "coke" are completely identical in composition, and "coke powder" refers to "coke" that exists in the form of a powder of a certain particle size, and "coke powder" is obtained by processing "coke" by crushing or other means.
[0056] In this specification, "dynamic carbon material raw material" and "dynamic carbon material raw material powder" are completely identical in composition, and "dynamic carbon material raw material powder" means "dynamic carbon material raw material" that exists in the form of a powder with a certain particle size. "Dynamic carbon material" means the product after graphitization and / or carbonization of "dynamic carbon material raw material" or "dynamic carbon material raw material powder".
[0057] As used herein, "amorphous carbon" refers to a transitional carbon material that has a low degree of graphitization crystallinity and is close to an amorphous form (or has no fixed shape or periodic structural order). As used herein, "amorphous carbon" refers to the product obtained after carbonization of an organic carbon source.
[0058] The key to improving the fast charging performance of secondary batteries is to improve the performance of the negative electrode sheet and the negative electrode active material. In order to improve the fast charging performance of secondary batteries, the prior art usually selects hard carbon as the negative electrode active material, but hard carbon has a relatively low gram capacity and compaction density, making it difficult for the secondary battery to have a high energy density, and the driving range of the electric vehicle is greatly shortened. If graphite is used as the negative electrode active material, the secondary battery can have a relatively high energy density, but the fast charging performance and low temperature output performance of the secondary battery are poor.
[0059] The present inventors, after much research, present a novel composite graphite material that can provide significantly improved rapid charging performance and low-temperature output performance under the premise of providing a secondary battery with high energy density.
[0060] Composite Graphite Materials A first aspect of the present embodiment provides a composite graphite material including bulk particles and a coating layer located on at least a part of the surface of the bulk particles, the bulk particles being secondary particles formed by agglomeration of two or more primary particles, the bulk particles including artificial graphite, the coating layer including amorphous carbon, and the composite graphite material having an air oxidation temperature T0 of 630° C. to 730° C. The air oxidation temperature T0 is a temperature corresponding to an intersection of two tangents to two points corresponding to 500° C. and the T1 temperature on the thermogravimetric curve of the composite graphite material, and the T1 temperature is a peak top temperature of a maximum area peak on a differential thermogravimetric curve of the composite graphite material, and the thermogravimetric curve and the differential thermogravimetric curve are obtained by thermogravimetric analysis under the conditions of a sample mass of 10±0.05 mg, air as a purge gas, a gas flow rate of 60 mL / min, a heating rate of 5° C. / min, and a measurement temperature range of 35° C. to 950° C.
[0061] The air oxidation temperature T0 can be determined by thermogravimetric analysis including the following steps: A composite graphite material is subjected to thermogravimetric measurement under the conditions of a weighed mass of 10±0.05 mg, a purge gas of air, a gas flow rate of 60 mL / min, a heating rate of 5°C / min, and a measurement temperature range of 35°C to 950°C, to obtain a thermogravimetric curve (also called a TG curve) and a differential thermogravimetric curve (also called a DTG curve), a peak top temperature T1 of the maximum area peak is read from the differential thermogravimetric curve, and an intersection point of two tangents of two points corresponding to 500°C and the T1 temperature on the thermogravimetric curve is determined, and the temperature corresponding to the intersection point on the thermogravimetric curve is the air oxidation temperature T0 of the composite graphite material.
[0062] The greater the number of graphite end faces and defects, the greater the number of sites in graphite where active ions can be inserted and removed, and the faster charging performance and low-temperature output performance of the secondary battery are improved. The inventors unexpectedly discovered that the number of graphite end faces and defects is closely related to the temperature at which graphite begins to lose weight due to air oxidation. The lower the temperature at which graphite begins to lose weight due to air oxidation, the greater the number of graphite end faces and defects, and the faster charging performance and low-temperature power of the secondary battery are improved.
[0063] The inventors unexpectedly discovered that the temperature corresponding to the intersection of the two tangents of the two points corresponding to 500°C and the peak top temperature T1 of the maximum area peak in the thermogravimetric curve, that is, the air oxidation temperature T0 of graphite, can accurately represent the temperature at which the weight loss due to air oxidation of graphite begins, and can also accurately reflect the number of end faces and defects of graphite. The composite graphite material of the first embodiment of the present application has an air oxidation temperature T0 of 630°C to 730°C, at this time, the number of end faces and defects contained in the composite graphite material is moderate, the composite graphite material has good active ion and electron transport performance, the charge exchange rate of active ions and electrons on the surface of the composite graphite material is relatively fast, and the active ion solid phase transport ability in the composite graphite material is relatively high, so that the secondary battery can have greatly improved fast charging performance and low temperature output performance under the premise of maintaining a high energy density. The inventors also discovered that conventional graphite has a relatively small interlayer distance, a relatively small number of end faces and defects, and a very high air oxidation temperature T0, making it difficult to improve the rapid charging performance and low-temperature output performance of a secondary battery.
[0064] In some embodiments, the air oxidation temperature T0 of the composite graphite material is 630°C to 730°C, 640°C to 730°C, 650°C to 730°C, 660°C to 730°C, 670°C to 730°C, 680°C to 730°C, 690°C to 730°C, 700°C to 730°C, 710°C to 730°C, 720°C to 730°C, 630°C to 720°C, 640°C to 720°C, 650°C to 720°C, 660°C to 720°C, 670°C to 720°C, 680°C to 720°C, 690°C to 720°C, 700°C to 720°C, 710°C to 720°C, 630°C to 710°C, 640°C to 710°C, 650°C to 720°C, ℃~710℃, 660℃~710℃, 670℃~710℃, 680℃~710℃, 690℃~710℃, 700℃~710℃, 630℃~700℃, 640℃~700℃, 650℃~700℃, 660℃~700℃, 670℃~700℃, 680℃~700℃, 690℃~700℃, 630℃~690℃, 640℃~690℃, 650℃~690℃, 660℃~690℃, 670℃~690℃, 680℃~690℃, 630℃~680℃, 640℃~680℃, 650℃~680℃, 660℃~680℃, or 670℃~680℃.
[0065] When the air oxidation temperature T0 of the composite graphite material is within a suitable range, the composite graphite material has a more suitable number of end faces and defects, and can further improve the transport performance of active ions and electrons, and improve the fast charging performance and low-temperature output performance of the secondary battery.
[0066] In some embodiments, the composite graphite material further comprises a dynamic carbon material, which in some embodiments is located at at least a portion of the interface between the primary particles in the bulk particles, in which case the bulk particles of the negative electrode active material comprise primary particles that are artificial graphite and the dynamic carbon material located between the primary particles.
[0067] In some embodiments, the dynamic carbon material is located in a coating layer, where the coating layer comprises amorphous carbon and the dynamic carbon material.
[0068] In some embodiments, the dynamic carbon material is located in both at least a portion of the interface between the primary particles in the bulk particle and in the coating layer.
[0069] 1-3 are schematic diagrams of different embodiments of the composite graphite material according to the present application. Referring to FIG. 1-3, the composite graphite material includes a bulk particle and a coating layer 102 located on at least a part of the surface of the bulk particle, and the bulk particle is a secondary particle formed by agglomeration of two or more primary particles 101. Referring to FIG. 1, the dynamic carbon material 103 may be located at at least a part of the interface between the primary particles 101 in the bulk particle; referring to FIG. 2, the dynamic carbon material 103 may further be located in the coating layer 102; referring to FIG. 3, the dynamic carbon material 103 may be located both at least a part of the interface between the primary particles 101 in the bulk particle and the coating layer 102.
[0070] In some embodiments, based on the total mass of the composite graphite material, the mass percent content of the dynamic carbon material is 1% to 30%. For example, the mass percent content of the dynamic carbon material is 3% to 30%, 3% to 25%, 3% to 20%, 3% to 15%, 5% to 30%, 5% to 25%, 5% to 20%, 5% to 15%, 8% to 30%, 8% to 25%, 8% to 20%, 8% to 15%, or 8% to 12%. The mass percent content of the dynamic carbon material is the sum of the mass percent content of the dynamic carbon material located at least in a portion of the interface between the primary particles in the bulk particle and the mass percent content of the dynamic carbon material located in the coating layer.
[0071] When the mass percent content of the dynamic carbon material is within a suitable range, the composite graphite material can have a relatively high active ion solid-phase transport ability and a relatively high charge exchange rate between active ions and electrons under the premise of having a high gram capacity, and the secondary battery can have a significantly improved fast charging performance and low-temperature output performance under the premise of having a high energy density.In addition, when the mass percent content of the dynamic carbon material is within a suitable range, the ability of maintaining the pore structure of the negative electrode membrane layer during the cycle process is higher, the electrolyte infiltration of the negative electrode sheet is better, and the secondary battery also has good cycle performance.
[0072] In some embodiments, the dynamic carbon material feedstock is one or more selected from hard carbon, fine expanded graphite, expanded graphite, and graphene.
[0073] Optionally, the hard carbon has a gram capacity of ≥ 320 mAh / g at 1 V or less, and a powder compaction density of ≥ 1.05 g / cm at 20,000 N applied force of the hard carbon. 3 It is.
[0074] Optionally, the dynamic carbon material raw material is one or more selected from micro-expanded graphite, expanded graphite, and in particular, the dynamic carbon material raw material is selected from expanded graphite.
[0075] In some embodiments, the interlayer distance d of the (002) crystal plane of the dynamic carbon material feedstock 002 ≧0.3358 nm. Optionally, the interlayer distance d of the (002) crystal plane of the dynamic carbon material raw material 002 is 0.3359nm to 0.3366nm.
[0076] The interlayer distance d of the dynamic carbon material raw material 002are both larger than those of general-purpose graphite, and when the dynamic carbon material obtained thereby is uniformly distributed in the bulk particles and / or coating layer of the composite graphite material, it is favorable for the rapid insertion and desorption of active ions, thereby improving the transport performance of active ions and electrons, and further improving the rapid charging performance and low-temperature output performance of the secondary battery, without causing a loss in the energy density of the secondary battery.
[0077] The dynamic carbon material raw material further has a relatively high pressure resistance, has a high ability to maintain the pore structure of the negative electrode membrane layer during the cycle process, and improves the electrolyte infiltration of the negative electrode sheet, thereby contributing to improving the cycle performance of the secondary battery.
[0078] In some embodiments, the interlayer spacing d of the (002) crystal planes of the composite graphite material 002 is 0.3355 nm to 0.3364 nm. Optionally, the interlayer distance d of the (002) crystal plane of the composite graphite material is 002 is 0.3356nm to 0.3361nm.
[0079] The composite graphite material has a relatively high interlayer distance d 002 By having such a structure, the active ion solid phase transport ability therein can be improved, and the rapid charging performance and low temperature output performance of the secondary battery can be improved.
[0080] In some embodiments, the composite graphite material has a volume average particle size Dv50 of 8.5 μm to 14.5 μm. Optionally, the composite graphite material has a volume average particle size Dv50 of 10 μm to 12 μm.
[0081] When the volume average particle diameter Dv50 of the composite graphite material is in an appropriate range, the composite graphite material has better active ion and electron transport performance and fast charging performance, and the composite graphite material can have a relatively high powder compaction density.
[0082] In some embodiments, the bulk particles have a volume average particle size Dv50 of 7.5 μm to 13.5 μm. Optionally, the bulk particles have a volume average particle size Dv50 of 9.0 μm to 11.5 μm.
[0083] When the volume average particle size Dv50 of the bulk particles of the composite graphite material is within a suitable range, the composite graphite material can have a higher gram capacity on the premise that it has better active ion and electron transport performance.
[0084] In some embodiments, the ratio of the volume average particle diameter Dv50 of the primary particles to the volume average particle diameter Dv50 of the secondary particles (i.e., bulk particles) formed therefrom is 0.45 to 0.75. Optionally, the ratio of the volume average particle diameter Dv50 of the primary particles to the volume average particle diameter Dv50 of the secondary particles formed therefrom is 0.55 to 0.65.
[0085] When the ratio of the volume average particle diameter Dv50 of the primary particles to the volume average particle diameter Dv50 of the secondary particles formed therefrom is within an appropriate range, the bulk particles of the composite graphite material have a relatively good degree of secondary particle size, which can improve the active ion and electron transport performance of the composite graphite material and have a relatively high structural stability. In addition, the bulk particles have a high ability to maintain the pore structure of the negative electrode membrane layer during the cycle process, and the electrolyte infiltration of the negative electrode sheet is better, which contributes to improving the cycle performance of the secondary battery.
[0086] In some embodiments, the weight percent content of amorphous carbon in the coating layer is 1% to 8% based on the total weight of the composite graphite material. Optionally, the weight percent content of amorphous carbon in the coating layer is 2% to 5%.
[0087] When the amorphous carbon content is within an appropriate range, the composite graphite material can have a high gram capacity and a relatively high active ion solid-phase transport capacity.
[0088] In some embodiments, at least a portion of the bulk particle surface is coated with a coating layer. Optionally, the composite graphite material includes bulk particles and a coating layer that covers at least 80% of the bulk particle surface. In particular, the composite graphite material includes bulk particles and a coating layer that covers at least 90% of the bulk particle surface.
[0089] In some embodiments, the composite graphite material has a powder compaction density of 1.45 g / cm at 20,000 N applied force. 3 ~1.75g / cm 3 Optionally, the powder compaction density of the composite graphite material at a force of 20,000 N is 1.55 g / cm 3 ~1.65g / cm 3 It is.
[0090] When the powder compaction density of the composite graphite material is within a suitable range, the negative electrode film layer has a relatively high compaction density, and the secondary battery can have a relatively high energy density. When the powder compaction density of the composite graphite material is within a suitable range, the ability of the negative electrode film layer to maintain its pore structure during cycling is high, and the negative electrode sheet has better electrolyte infiltration, which also contributes to improving the cycle performance of the secondary battery.
[0091] In this application, the volume average particle size Dv50 of a material has the meaning known in the art, and refers to the particle size when the cumulative volume distribution percentage of the material reaches 50%, and can be measured by the machine and method known in the art. For example, see GB / T 19077-2016 Particle size distribution laser diffraction method, and can be conveniently measured by using a laser particle size analyzer, such as the Mastersizer 2000E type laser particle size analyzer of Malvern Instruments Ltd. in the UK.
[0092] In this application, the layer distance d 002has a meaning known in the art and can be measured by a device and method known in the art. For example, see JIS K 0131-1996, JB / T 4220-2011, and can be measured by using an X-ray powder diffractometer (e.g., PANalytical X'pert PRO). 002 can be measured.
[0093] In this application, the powder compaction density of a material has a meaning known in the art and can be measured by a machine and method known in the art. For example, it can be measured by an electronic pressure tester (e.g., UTM7305 type) with reference to standard GB / T24533-2009. As an exemplary measurement method, 1 g of the material is weighed and the base area is 1.327 cm 2 The powder is placed in a mold, pressurized to 2000 kg (corresponding to 20000 N), pressure is maintained for 30 s, and the pressure is released and maintained for 10 s, and the powder density of the material is recorded and calculated at 20000 N applied force.
[0094] In this application, the gram capacity of a material has a meaning known in the art and can be measured by a method known in the art. As an exemplary measurement method, the material to be measured, carbon black (Super P) as a conductive agent, and polyvinylidene fluoride (PVDF) as a binder are uniformly mixed with N-methylpyrrolidone (NMP) as a solvent in a mass ratio of 91.6:1.8:6.6 to prepare a slurry, and the prepared slurry is applied to a copper foil current collector and dried in an oven. A metallic lithium sheet is used as a counter electrode, and a polyethylene (PE) film is used as a separator. Ethylene carbonate (EC), methyl ethyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1, and LiPF6 is uniformly dissolved in the solution to obtain an electrolyte solution, with the concentration of LiPF6 being 1 mol / L. A CR2430 button cell is assembled in an argon gas protected glove box. The obtained button battery is left to stand for 12 hours, then discharged at 25°C with a constant current of 0.05C to 0.005V, left to stand for 10 minutes, and discharged at a constant current of 50μA to 0.005V, left to stand for 10 minutes, discharged at a constant current of 10μA to 0.005V, and charged at a constant current of 0.1C to 2V, and the charge capacity is recorded. The ratio of the charge capacity to the mass of the material is the gram capacity of the material.
[0095] Method for preparing composite graphite material A second aspect of the present embodiment provides a method for preparing a composite graphite material, comprising the steps of: S10: providing coke powder or coke powder to which a dynamic carbon material raw powder is added, and graphitizing the coke powder or the coke powder to which the dynamic carbon material raw powder is added to obtain bulk particles, the bulk particles being secondary particles formed by agglomeration of two or more primary particles, and the bulk particles including artificial graphite; and S20: mixing the bulk particles with an organic carbon source, or mixing the bulk particles with an organic carbon source and the dynamic carbon material raw powder, and carbonizing the bulk particles to form a coating layer including amorphous carbon on at least a part of the surface of the bulk particles, thereby obtaining the composite graphite material.
[0096] The dynamic carbon material raw material powder is added in at least one of steps S10 and S20, and the dynamic carbon material raw material is one or more selected from hard carbon, fine expanded graphite, expanded graphite, and graphene, and the interlayer distance d of the dynamic carbon material raw material (002) crystal plane is 002 ≧0.3358 nm.
[0097] The obtained composite graphite material has an air oxidation temperature T0 of 630°C to 730°C, the air oxidation temperature T0 being the temperature corresponding to the intersection of two tangents to two points corresponding to 500°C and the T1 temperature, respectively, on the thermogravimetric curve of the composite graphite material, and the T1 temperature being the peak top temperature of the maximum area peak on the differential thermogravimetric curve of the composite graphite material, and the thermogravimetric curve and the differential thermogravimetric curve are obtained by thermogravimetric analysis under conditions of a sample mass of 10±0.05 mg, air as a purge gas, a gas flow rate of 60 mL / min, a heating rate of 5°C / min, and a measurement temperature range of 35°C to 950°C.
[0098] Specifically, the air oxidation temperature T0 is determined by thermogravimetric analysis including the following steps: A thermogravimetric measurement is performed under the conditions of a weighed mass of 10±0.05 mg, a purge gas of air, a gas flow rate of 60 mL / min, a heating rate of 5°C / min, and a measurement temperature range of 35°C to 950°C to obtain a thermogravimetric curve and a differential thermogravimetric curve, a peak top temperature T1 of the maximum area peak is read from the differential thermogravimetric curve, and an intersection point of two tangents to two points corresponding to 500°C and the T1 temperature on the thermogravimetric curve is determined, and the temperature corresponding to the intersection point on the thermogravimetric curve is the air oxidation temperature T0 of the composite graphite material.
[0099] The method for preparing the composite graphite material according to the present invention is simple in operation, low in cost, and suitable for large-scale industrial production.
[0100] The method of the present application provides a composite graphite material with a moderate content of edges and defects, and the secondary battery can have significantly improved fast charging performance and low temperature output performance under the premise of having a high energy density.
[0101] In some embodiments, the hard carbon has a gram capacity at 1 V or less of ≧320 mAh / g and a powder compaction density at 20,000 N applied force of ≧1.05 g / cm 3 It is.
[0102] In some embodiments, the dynamic carbon material raw material is one or more selected from fine expanded graphite, expanded graphite. Optionally, the dynamic carbon material raw material is selected from expanded graphite.
[0103] In some embodiments, the interlayer distance d of the (002) crystal plane of the dynamic carbon material feedstock 002 is 0.3359nm to 0.3366nm.
[0104] In some embodiments, a method for providing coke powder includes coking a coke feedstock to obtain coke, and crushing, forming, and classifying the coke to obtain coke powder.
[0105] In some embodiments, the coke is obtained directly from a commercial source.
[0106] Optionally, the coke raw material may be one or more selected from petroleum-based raw materials and coal-based raw materials. For example, the petroleum-based raw material is one or more selected from heavy oil, residual oil, and vacuum residual oil, and the coal-based raw material is mainly selected from coal asphalt. Heavy oil, residual oil, and vacuum residual oil are usually produced in a petroleum refining process, and coal asphalt is usually produced in a coal carbonization process.
[0107] In some embodiments, the coke comprises one or more of petroleum-based non-acicular coke, petroleum-based needle coke, coal-based non-acicular coke, and coal-based needle coke. Optionally, the coke comprises one or more of petroleum-based non-acicular coke (e.g., calcined petroleum coke, petroleum-based raw coke), and petroleum-based needle coke. In particular, the coke comprises petroleum-based raw coke. By adopting a suitable coke, the prepared composite graphite material has a suitable number of end faces and defects, and further has relatively good active ion and electron transport performance and relatively high structural stability, so that the fast charging performance, low temperature output performance, and cycle performance of the secondary battery can be improved.
[0108] Optionally, the coke feedstock is coked in a delayed coking device, which includes a furnace and a coke tower, and the delayed coking process refers to first rapidly heating the coke feedstock to a desired coking temperature in the furnace, then entering the coke tower, and producing coke through processes such as preheating, cold coking, etc. in the coke tower.
[0109] The coke can be crushed using equipment and methods known in the art, such as an air mill, a mechanical mill, a roll mill, or other crushing equipment.
[0110] The morphology of the coke powder obtained by crushing may include one or more of agglomerate, spherical, and near-spherical. After crushing is completed, the edges and corners of the coke powder are polished to form it. The greater the degree of forming, the closer the powder particles are to a sphere, which can increase the number of insertion and desorption sites for active ions on the surface of the composite graphite material. The forming process is also advantageous for the subsequent granulation process, and can provide the secondary particles in the obtained composite graphite material with relatively high structural stability.
[0111] The coke powder can be processed by molding using equipment and methods known in the art, such as a molding machine or other molding equipment.
[0112] During the crushing and molding process, too small particles are often generated, and sometimes too large particles exist, so that the powder can be classified to remove too small or too large particles as necessary. After the classification process, the coke powder with better particle size distribution can be obtained, which facilitates the subsequent granulation and coating process. The classification process can be carried out by adopting equipment and methods known in the art, such as a classification sieve, a gravity classifier, and a centrifugal classifier.
[0113] In some embodiments, the coke powder has a volume average particle size Dv50 of 6 μm to 12 μm. Optionally, the coke powder has a volume average particle size Dv50 of 8 μm to 10 μm.
[0114] In some embodiments, the method for providing a dynamic carbon material raw material powder includes crushing, forming, and classifying the dynamic carbon material raw material to obtain a dynamic carbon material raw material powder, and the crushing, forming, and classifying methods are the same as the crushing, forming, and classifying methods of the coke.
[0115] In some embodiments, the dynamic carbon material raw powder has a volume average particle size Dv50 of 3 μm to 12 μm.Optionally, the dynamic carbon material raw powder has a volume average particle size Dv50 of 4 μm to 9 μm.
[0116] In some embodiments, the ratio of the volume average particle diameter Dv50 of the coke powder to the volume average particle diameter Dv50 of the dynamic carbon material raw powder is 1.05 to 1.75. Optionally, the ratio of the volume average particle diameter Dv50 of the coke powder to the volume average particle diameter Dv50 of the dynamic carbon material raw powder is 1.2 to 1.5. When the ratio of the volume average particle diameter Dv50 of the coke powder to the volume average particle diameter Dv50 of the dynamic carbon material raw powder is within a suitable range, the bulk particles of the composite graphite material can have a relatively good degree of secondary particles.
[0117] In some embodiments, in the coke powder added with the dynamic carbon material raw material powder, the mass ratio of the coke powder to the dynamic carbon material raw material powder is 1-20:99-80. Optionally, the mass ratio of the coke powder to the dynamic carbon material raw material powder is 3-12:97-88. When the mass ratio of the coke powder to the dynamic carbon material raw material powder is within a suitable range, it is favorable to obtain a composite graphite material with a suitable content of edge and defect, and further, the secondary battery can have greatly improved fast charging performance and low temperature output performance under the premise of having high energy density.
[0118] In some embodiments, based on the total mass of the obtained composite graphite material, the sum of the mass percentage content of the dynamic carbon material raw material powder added in steps S10 and S20 is 1%-30%, for example, 3%-30%, 3%-25%, 3%-20%, 3%-15%, 5%-30%, 5%-25%, 5%-20%, 5%-15%, 8%-30%, 8%-25%, 8%-20%, 8%-15%, or 8%-12%.
[0119] In some embodiments, the method further comprises adding a binder to S10, mixing the binder with the coke powder, granulating, and graphitizing to obtain bulk particles, or mixing the binder with the coke powder and adding the kinetic carbon material raw material powder, granulating, and graphitizing to obtain bulk particles.
[0120] By adding a binder, the bulk particles of the composite graphite material can have a relatively good degree of secondary particles, which improves the transport performance of active ions and electrons of the composite graphite material and allows it to have relatively high structural stability.
[0121] Optionally, based on the total mass of the obtained composite graphite material, the mass percent content of the binder is 3% to 12%. Further, optionally, the mass percent content of the binder is 5% to 8%. When the binder content is within a suitable range, excessive particle aggregation can be avoided, and the bulk particles of the composite graphite material can have a relatively good degree of secondary particles.
[0122] Optionally, the binder is selected from asphalt. Optionally, the asphalt has a softening point of 200° C. or higher.
[0123] Optionally, the asphalt is one or more selected from coal asphalt, petroleum asphalt.
[0124] Optionally, the particles obtained by granulation have a volume average particle diameter Dv50 of 8 μm to 14 μm. In particular, the particles obtained by granulation have a volume average particle diameter Dv50 of 9.5 μm to 12 μm.
[0125] Granulation may be performed using equipment and methods known in the art, such as a granulator. The granulator usually includes a stirring reaction kettle and a module for controlling the temperature of the reaction kettle. By controlling the stirring rotation speed, heating rate, granulation temperature, and temperature drop rate during the granulation process, the degree of granulation and the structural strength of the particles can be controlled, and the volume average particle size Dv50 of the bulk particles of the finally produced composite graphite material can be set within a desired range.
[0126] In some embodiments, in S10, the graphitization temperature may be 2800° C. to 3200° C. Optionally, the graphitization temperature may be 2900° C. to 3100° C. The graphitization can provide the bulk particles with a suitable graphitization degree, and the composite graphite material can have a relatively high gram capacity; the graphitization can also reduce the lattice expansion of the bulk particles during the insertion and desorption process of active ions; the graphitization can effectively eliminate the bulk phase structural defects of the bulk particles, and improve the cycle performance of the secondary battery.
[0127] In some embodiments, the graphitization treatment time in S10 is 10 to 15 days.
[0128] The graphitization may be performed using equipment and methods known in the art, such as a graphitization furnace, particularly an Acheson graphitization furnace. After the graphitization process is completed, a small amount of excessively large particles formed by agglomeration of the granulated product during the graphitization process may be removed by sieving, thereby preventing the excessively large particles from affecting the processing performance of the composite graphite material, such as the stability and coating performance of the negative electrode slurry.
[0129] In some embodiments, the volume average particle diameter Dv50 of the bulk particles obtained in S10 is 7.5 μm to 13.5 μm. Optionally, the volume average particle diameter Dv50 of the bulk particles obtained is 9.0 μm to 11.5 μm.
[0130] In some embodiments, in S20, the organic carbon source is one or more of coal asphalt, petroleum asphalt, phenolic resin, and coconut shell. Optionally, the organic carbon source is selected from petroleum asphalt. Optionally, the softening point of the coal asphalt or petroleum asphalt is 250° C. or less.
[0131] In some embodiments, the amount of organic carbon source added is such that the weight percent content of amorphous carbon obtained by carbonizing the organic carbon source is 1% to 8% based on the total weight of the resulting composite graphite material. Optionally, the amount of organic carbon source added is such that the weight percent content of amorphous carbon obtained by carbonizing the organic carbon source is 2% to 5%. When the amount of organic carbon source added is within an appropriate range, the composite graphite material can have a high gram capacity and a relatively high active ion solid phase transport capacity.
[0132] In some embodiments, in S20, the carbonization temperature is 700° C. to 1800° C. Optionally, the carbonization temperature is 1000° C. to 1300° C. When the carbonization temperature is within an appropriate range, the organic carbon source (and any dynamic carbon material raw material) can be carbonized, and a coating layer containing amorphous carbon can be formed on at least a portion of the surface of the artificial graphite.
[0133] In some embodiments, the carbonization treatment time in S20 is 1 hour to 6 hours.
[0134] In some embodiments, the method for preparing the composite graphite material includes the steps of: S10: providing coke powder and dynamic carbon material raw powder, mixing a binder with the coke powder and the dynamic carbon material raw powder to granulate, and graphitizing to obtain bulk particles, the bulk particles being secondary particles formed by agglomeration of two or more primary particles, the bulk particles including artificial graphite; and S20: mixing the bulk particles with an organic carbon source, carbonizing to form a coating layer including amorphous carbon on at least a part of the surface of the bulk particles to obtain a composite graphite material.
[0135] In some embodiments, the method for preparing the composite graphite material includes the steps of: S10: providing coke powder, mixing a binder with the coke powder to granulate, and graphitizing to obtain bulk particles, the bulk particles being secondary particles formed by agglomeration of two or more primary particles, the bulk particles including artificial graphite; and S20: mixing the bulk particles with an organic carbon source and a kinetic carbon material raw material powder, and carbonizing to form a coating layer including amorphous carbon on at least a portion of the surface of the bulk particles to obtain the composite graphite material.
[0136] In some embodiments, the method for preparing the composite graphite material includes the steps of: S10: providing coke powder and dynamic carbon material raw powder, mixing a binder with the coke powder and the dynamic carbon material raw powder to granulate, and graphitizing to obtain bulk particles, the bulk particles being secondary particles formed by agglomeration of two or more primary particles, the bulk particles including artificial graphite; and S20: mixing the bulk particles with an organic carbon source and the dynamic carbon material raw powder, and carbonizing to form a coating layer including amorphous carbon on at least a part of the surface of the bulk particles to obtain a composite graphite material.
[0137] In the preparation method according to the present application, coke powder or coke powder to which dynamic carbon material raw powder is added is graphitized to obtain bulk particles, and the bulk particles are secondary particles formed by agglomeration of two or more primary particles. The coke powder obtained through processes such as pulverization and molding is mainly a single particle, and in terms of morphology, the coke powder is a primary particle (or primary particle), while the bulk particles obtained by granulating the coke powder or coke powder to which dynamic carbon material raw powder is added and graphitizing the same are agglomerates of a plurality of the primary particles, and therefore in terms of morphology, the bulk particles are secondary particles.
[0138] In the preparation method of the present application, by adjusting the volume average particle diameter Dv50 of the coke powder and its added amount, the volume average particle diameter Dv50 of the dynamic carbon material raw material powder and its added amount, the added amount of the binder, the added amount of the organic carbon source, etc., a composite graphite material having a different air oxidation temperature T0 can be obtained.
[0139] secondary battery A secondary battery is also called a rechargeable battery or storage battery, and is a battery that can be discharged and then recharged to activate the active material so that it can be used again.
[0140] Typically, a secondary battery includes a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte. During the charge and discharge process of the battery, active ions are repeatedly inserted and removed between the positive electrode sheet and the negative electrode sheet. The separator is placed between the positive electrode sheet and the negative electrode sheet, and its main role is to prevent short circuits between the positive and negative electrodes and to allow the passage of ions. The electrolyte serves to conduct active ions between the positive and negative electrode sheets.
[0141] [Negative electrode sheet] In the secondary battery according to the present application, the negative electrode sheet includes a negative electrode current collector and a negative electrode film layer located on at least one surface of the negative electrode current collector. For example, the negative electrode current collector has two surfaces facing each other in its thickness direction, and the negative electrode film layer is disposed on either one or both of the two facing surfaces of the negative electrode current collector.
[0142] The negative electrode current collector may be a metal foil sheet or a composite current collector. An example of the metal foil sheet may be copper foil. The composite current collector may include a polymer base layer and a metal material layer formed on at least one surface of the polymer base layer. For example, the metal material may be one or more selected from copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy. For example, the polymer base layer may be selected from polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.
[0143] The negative electrode film layer usually includes a negative electrode active material, an optional binder, an optional conductive agent, and other optional auxiliary agents. The negative electrode film layer is usually obtained by applying a negative electrode slurry onto a negative electrode current collector, drying, and cold rolling. The negative electrode slurry is usually formed by dispersing the negative electrode active material, the optional conductive agent, the optional binder, and other optional auxiliary agents in a solvent and stirring the mixture uniformly. The solvent may be, but is not limited to, N-methylpyrrolidone (NMP) or deionized water.
[0144] In some embodiments, the negative electrode active material may comprise one of the composite graphite material of the first aspect of the present embodiment and the composite graphite material prepared by the method of the second aspect of the present embodiment.
[0145] In some embodiments, the negative electrode active material may further include other negative electrode active materials used in secondary batteries known in the art. For example, the other negative electrode active materials may include one or more of natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. The silicon-based materials may include one or more of elemental silicon, silicon oxide, silicon-carbon composites, silicon-nitrogen composites, and silicon alloy materials. The tin-based materials may include one or more of elemental tin, tin oxide, and tin alloy materials. The present application is not limited to these materials, and other known traditional materials used as negative electrode active materials in secondary batteries may be used. These other negative electrode active materials may be used alone or in combination of two or more.
[0146] In some embodiments, the conductive agent may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, the binder may include one or more of styrene butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid (PAA)), polymethacrylic acid (PMAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and chitosan carboxylate methyl (CMCS). In some embodiments, other optional auxiliary agents may include thickeners (e.g., sodium carboxymethyl cellulose (CMC-Na), PTC thermistor materials, etc.).
[0147] In some embodiments, the negative electrode film layer may further include an additive. In this case, the additive, the composite graphite material, an optional conductive agent, an optional binder, and other optional auxiliary agents may be dispersed in a solvent and uniformly stirred to form a negative electrode slurry, and the negative electrode slurry may be applied to a negative electrode current collector, dried, and cold rolled to form a negative electrode film layer. The additive may be one or more selected from hard carbon, fine expanded graphite, expanded graphite, and graphene, and the interlayer distance d of the (002) crystal plane of the additive may be 0.01 to 0.01. 002 ≧0.3358 nm. These additives have relatively good active ion and electron transport properties, and can greatly improve the fast charging performance and low temperature output performance under the premise of making the secondary battery have high energy density.
[0148] Optionally, the hard carbon has a gram capacity of ≧320 mAh / g at ≦1 V, and a powder compaction density of ≧1.05 g / cm at 20,000 N applied force. 3 It is.
[0149] Optionally, the additive is one or more selected from fine expanded graphite, expanded graphite, particularly, the additive is selected from expanded graphite.
[0150] Optionally, the interlayer distance d of the additive (002) crystal plane 002 is 0.3359nm to 0.3366nm.
[0151] Optionally, based on the total mass of the negative electrode film layer, the mass percentage content of the additive is 1% to 20%. For example, the mass percentage content of the additive is 1% to 20%, 1% to 18%, 1% to 15%, 1% to 12%, 1% to 10%, 1% to 8%, 1% to 5%, 2% to 20%, 2% to 18%, 2% to 15%, 2% to 12%, 2% to 10%, 2% to 8%, 2% to 5%, 3% to 20%, 3% to 18%, 3% to 15%, 3% to 12%, 3% to 10%, 3% to 8%, or 3% to 5%. When the mass percentage content of the additive is within a suitable range, the secondary battery can have a significantly improved fast charging performance and low temperature output performance under the premise of having a high energy density. In addition, when the mass percent content of the additive is within an appropriate range, the ability of the negative electrode membrane layer to maintain its pore structure during cycling is higher, and the electrolyte infiltration of the negative electrode sheet is better, so that the secondary battery has good cycle performance.
[0152] In some embodiments, the negative electrode membrane layer has an areal density of 0.035 kg / m 2 ~0.125kg / m 2 Optionally, the negative electrode film layer has an areal density of 0.078 kg / m 2 ~0.107kg / m 2 It is.
[0153] When the areal density of the negative electrode film layer is within the above-mentioned range, the negative electrode sheet has a relatively high reversible capacity and a relatively low impedance for transporting active ions and electrons, which can further improve the energy density, rapid charging performance, low-temperature output performance and cycle performance of the secondary battery.
[0154] In this application, the areal density of the negative electrode film layer has a meaning known in the art and can be measured by a method known in the art. For example, a negative electrode sheet coated on one side and cold rolled (in the case of a negative electrode sheet coated on both sides, the negative electrode film layer on one side may be wiped off) is punched into a small disk with an area of S1, weighed, and recorded as M1. Then, the negative electrode film layer of the weighed negative electrode sheet is wiped off, and the weight of the negative electrode current collector is weighed and recorded as M0. The areal density of the negative electrode film layer=(M1-M0) / S1.
[0155] In some embodiments, the negative electrode membrane layer has a packed density of 1.2 g / cm 3 ~1.75g / cm 3 Optionally, the negative electrode membrane layer has a packed density of 1.4 g / cm 3 ~1.6g / cm 3 It is.
[0156] When the compaction density of the negative electrode film layer is within the aforementioned range, the negative electrode sheet has a relatively high reversible capacity, and further has a relatively low cycle expansion and good dynamic performance, so that the energy density, fast charging performance, low temperature output performance and cycle performance of the secondary battery can be further improved.
[0157] In this specification, the compaction density of the negative electrode film layer has a meaning known in the art and can be measured by a method known in the art. Compaction density of the negative electrode film layer = surface density of the negative electrode film layer / thickness of the negative electrode film layer. In this application, the thickness of the negative electrode film layer has a meaning known in the art and can be measured by a method known in the art. For example, a spiral micrometer with 4-bit accuracy is adopted.
[0158] In some embodiments, the negative electrode membrane layer has a porosity of 25% to 45%. Optionally, the negative electrode membrane layer has a porosity of 28% to 35%.
[0159] When the porosity of the negative electrode film layer is within the above range, the negative electrode sheet has suitable electrolyte infiltration and good reaction interface, which improves the charge / discharge performance of the negative electrode at a large charge ratio, and can improve the rapid charge performance of the secondary battery. In addition, since the negative electrode film layer has a suitable electrolyte retention amount, the mass of the secondary battery is relatively low, which is advantageous for the secondary battery to have a relatively high mass energy density.
[0160] In this application, the porosity of the negative electrode film layer has a meaning known in the art and can be measured by a method known in the art. For example, it can be measured by gas displacement method with reference to GB / T24586-2009. The measurement method is to punch a small disk sample with a diameter of 14 mm from the negative electrode sheet after one side is coated and cold-rolled (for a negative electrode sheet coated on both sides, the negative electrode film layer on one side may be wiped off first), measure the thickness of the negative electrode film layer (thickness of the negative electrode sheet-thickness of the negative electrode current collector), calculate the apparent volume V1 of the negative electrode film layer according to the cylinder volume calculation formula, use an inert gas, such as helium or nitrogen gas, as the medium, adopt the gas displacement method, and use a true density measuring device (such as Micromeritics AccuPyc II 1340 type) to measure the true volume of the negative electrode sheet, and the measurement can be performed with reference to GB / T 24586-2009, and obtain the true volume V2 of the negative electrode film layer by subtracting the volume of the negative electrode current collector from the true volume of the negative electrode sheet. Porosity of negative electrode membrane layer = (V1 - V2) / V1 x 100%. A number of negative electrode sheet samples (for example, 30 sheets) are measured and the average value is used as the result, which can improve the accuracy of the measurement result.
[0161] In some embodiments, the adhesive strength between the negative electrode film layer and the negative electrode current collector is 4.5 N / m to 15 N / m. Optionally, the adhesive strength between the negative electrode film layer and the negative electrode current collector is 8 N / m to 12 N / m.
[0162] When the adhesive strength between the negative electrode film layer and the negative electrode current collector is within the above-mentioned range, the fast charging performance and cycle performance of the secondary battery can be improved. When the adhesive strength between the negative electrode film layer and the negative electrode current collector is large, the negative electrode sheet has good electronic conductivity, which is favorable for improving the insertion rate of active ions. In addition, the adhesive strength between the negative electrode film layer and the negative electrode current collector can further reflect the ability of the negative electrode sheet to maintain adhesive reliability during the cycle process, which is favorable for the secondary battery to maintain good electronic conductivity throughout the entire life cycle, and can further improve the cycle performance of the secondary battery.
[0163] In this application, the adhesive force between the negative electrode film layer and the negative electrode current collector has a meaning known in the art and can be measured by a method known in the art. As an exemplary measurement method, the negative electrode sheet is cut into a measurement sample of 100 mm in length and 10 mm in width, a stainless steel plate of 25 mm in width is taken, a double-sided tape (width 11 mm) is attached, the measurement sample is attached to the double-sided tape on the stainless steel plate, the surface is repeatedly rolled three times (300 mm / min) using a 2000 g roller, the measurement sample is bent 180 degrees, and the negative electrode film layer and the negative electrode current collector of the measurement sample are manually peeled off by 25 mm, the measurement sample is fixed to a test machine (e.g., INSTRON 336) so that the peeling surface coincides with the force line of the test machine, and the test machine is used to continuously peel off at 30 mm / min, and the average value of the smooth fracture is taken as the peel force F0 from the obtained peel force curve. The adhesive force between the negative electrode film layer and the current collector = F0 / width of the measurement sample.
[0164] In this application, the relevant parameters of the negative electrode film layer all refer to the parameters of one side of the negative electrode film layer, that is, when the negative electrode film layer is disposed on two sides of the negative electrode current collector, if the parameters of the negative electrode film layer on either side meet the parameter range of this application, it is considered to be within the protection scope of this application.
[0165] In the secondary battery according to the present application, the negative electrode sheet does not exclude additional functional layers other than the negative electrode film layer. For example, in some embodiments, the negative electrode sheet according to the present application further includes a conductive underlayer (e.g., made of a conductive agent and a binder) sandwiched between the negative electrode current collector and the negative electrode film layer and disposed on the surface of the negative electrode current collector. In other embodiments, the negative electrode sheet according to the present application further includes a protective layer covering the surface of the negative electrode film layer.
[0166] [Positive electrode sheet] In the secondary battery according to the present application, the positive electrode sheet includes a positive electrode current collector and a positive electrode film layer provided on at least one surface of the positive electrode current collector and including a positive electrode active material. For example, the positive electrode current collector has two surfaces facing each other in its thickness direction, and the positive electrode film layer is disposed on either one or both of the two facing surfaces of the positive electrode current collector.
[0167] In the secondary battery according to the present application, the positive electrode active material may be a positive electrode active material for secondary batteries known in the art. For example, the positive electrode active material may include one or more of lithium transition metal oxides, lithium-containing phosphates with an olivine structure, and their respective modified compounds. Examples of lithium transition metal oxides may include, but are not limited to, one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their respective modified compounds. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, one or more of lithium iron phosphate, lithium iron phosphate and carbon composite material, lithium manganese phosphate, lithium manganese iron phosphate, lithium manganese iron phosphate and carbon composite material, and their respective modified compounds. In the present application, the present application is not limited to these materials, and other traditional materials known as positive electrode active materials for secondary batteries may be used.
[0168] In some embodiments, in order to further increase the energy density of the secondary battery, the positive electrode active material may include one or more of the lithium transition metal oxides and modified compounds thereof represented by Formula 1.
[0169] Li a Ni b Co c M d O e A f Formula 1 In Formula 1, 0.8 ≦ a ≦ 1.2, 0.5 ≦ b < 1, 0 < c < 1, 0 < d < 1, 1 ≦ e ≦ 2, 0 ≦ f ≦ 1, M is one or more selected from Mn, Al, Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, and B, and A is one or more selected from N, F, S, and Cl.
[0170] In the present application, the modified compound of each of the above-described materials may be a material obtained by doping modification or surface coating modification of the positive electrode active material.
[0171] In the secondary battery according to the present application, the positive electrode film layer usually includes a positive electrode active material, an optional binder, and an optional conductive agent. The positive electrode film layer is usually formed by applying a positive electrode slurry to a positive electrode current collector, drying, and cold rolling. The positive electrode slurry is usually formed by dispersing a positive electrode active material, an optional conductive agent, an optional binder, and any other components in a solvent and stirring them uniformly. The solvent may be N-methylpyrrolidone (NMP), but is not limited thereto. As an example, the binder used for the positive electrode film layer may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0172] In the secondary battery according to the present application, the positive electrode current collector may be a metal foil sheet or a composite current collector. An example of the metal foil sheet may be aluminum foil. The composite current collector may include a polymer base layer and a metal material layer formed on at least one surface of the polymer base layer. For example, the metal material may be one or more selected from aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy. For example, the polymer base layer may be selected from polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), and the like.
[0173] [Electrolyte] The secondary battery according to the present application is not specifically limited in the type of electrolyte, and can be selected according to needs. For example, the electrolyte may be at least one selected from a solid electrolyte and a liquid electrolyte (i.e., an electrolytic solution).
[0174] In some embodiments, the electrolyte is an electrolytic solution that includes an electrolyte salt and a solvent.
[0175] In the present application, there is no specific limitation on the type of electrolyte salt, and it can be selected according to needs. In some embodiments, as an example, the electrolyte salt may be one or more selected from LiPF6 (lithium hexafluorophosphate), LiBF4 (lithium tetrafluoroborate), LiClO4 (lithium perchlorate), LiAsF6 (lithium hexafluoroarsenate), LiFSI (lithium bis(fluorosulfonyl)imide), LiTFSI (lithium bis(trifluoromethanesulfonyl)imide), LiTFS (lithium trifluoromethanesulfonate), LiDFOB (lithium difluoro(oxalate)borate), LiBOB (lithium bis(oxalate)borate), LiPO2F2 (lithium difluorophosphate), LiDFOP (lithium difluorobis(oxalate)phosphate) and LiTFOP (lithium tetrafluoro(oxalate)phosphate).
[0176] In the present application, there is no specific limitation on the type of solvent, which can be selected according to needs. In some embodiments, by way of example, the solvent may be one or more selected from ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), and diethyl sulfone (ESE).
[0177] In some embodiments, the electrolyte may further include an optional additive. For example, the additive may include an anode film-forming additive, a cathode film-forming additive, or an additive that can improve certain performance of the battery, such as an additive that improves the overcharge performance of the battery, an additive that improves the high temperature performance of the battery, or an additive that improves the low temperature performance of the battery.
[0178] [Separator] Some secondary batteries using an electrolyte and some secondary batteries using a solid electrolyte further include a separator. The separator is provided between the positive electrode sheet and the negative electrode sheet and plays a role of isolation. In the present application, the type of separator is not particularly limited, and any separator having a porous structure with good known chemical stability and mechanical stability can be selected and used. In some embodiments, the material of the separator may be at least one or more selected from glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator may be a single layer film or a multilayer composite film. When the separator is a multilayer composite film, the materials of each layer may be the same or different.
[0179] In some embodiments, the positive electrode sheet, the separator, and the negative electrode sheet can be made into an electrode assembly by a winding process or a stacking process.
[0180] In some embodiments, the secondary battery may include an exterior case that is used to seal the electrode assembly and electrolyte.
[0181] In some embodiments, the exterior of the secondary battery may be a hard case such as a hard plastic case, an aluminum case, a steel case, etc. The exterior of the secondary battery may be a soft bag such as a pouch-type soft bag. The material of the soft bag may be one or more types of plastic such as polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc.
[0182] In the present application, the shape of the secondary battery is not particularly limited and may be cylindrical, rectangular or any other shape. For example, FIG. 4 shows a secondary battery 5 having a rectangular structure as an example.
[0183] In some embodiments, referring to FIG. 5, the exterior may include a case 51 and a cover plate 53. The case 51 includes a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate may be surrounded to form a receiving cavity. The case 51 has an opening communicating with the receiving cavity, and the cover plate 53 is used to cover the opening so as to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the separator may be formed into an electrode assembly 52 by a winding process or a lamination process. The electrode assembly 52 is sealed in the receiving cavity. The electrolyte is impregnated in the electrode assembly 52. The number of electrode assemblies 52 included in the secondary battery 5 may be one or more, and may be adjusted according to needs.
[0184] In some embodiments, the secondary batteries can be assembled into a battery module, and the number of secondary batteries included in the battery module can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module.
[0185] Fig. 6 shows an example of a battery module 4. Referring to Fig. 6, in the battery module 4, the multiple secondary batteries 5 may be arranged in order along the longitudinal direction of the battery module 4. Of course, they may be arranged in any other manner. Furthermore, the multiple secondary batteries 5 may be fixed by a fastener.
[0186] Optionally, the battery module 4 further includes a housing having an accommodating space, and the multiple secondary batteries 5 are accommodated in the accommodating space.
[0187] In some embodiments, the battery modules can be further assembled into a battery pack, and the number of battery modules included in the battery pack can be adjusted according to the application and capacity of the battery pack.
[0188] 7 and 8 show an example of a battery pack 1. Referring to FIG. 7 and FIG. 8, the battery pack 1 may include a battery housing and a plurality of battery modules 4 disposed in the battery housing. The battery housing includes an upper housing 2 and a lower housing 3, and the upper housing 2 is disposed over the lower housing 3 and is used to form a sealed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in any manner within the battery housing.
[0189] The method for preparing the secondary battery according to the present application is known. In some embodiments, a positive electrode sheet, a separator, a negative electrode sheet, and an electrolyte are assembled to form a secondary battery. For example, the positive electrode sheet, the separator, and the negative electrode sheet are formed into an electrode assembly by a winding process or a lamination process, the electrode assembly is placed in an outer package, dried, and then the electrolyte is injected, and the secondary battery is obtained through processes such as vacuum sealing, standing, chemical formation, and molding.
[0190] Electrical equipment The present embodiment further provides an electric device including at least one of the secondary batteries, battery modules, or battery packs according to the present application. The secondary batteries, battery modules, or battery packs may be used as a power source for the electric device, or may be used as an energy storage unit for the electric device. The electric device may be, but is not limited to, a mobile device (e.g., a mobile phone, a laptop, etc.), an electric vehicle (e.g., a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), a train, a ship, a satellite, an energy storage system, etc.
[0191] The electric device can select a secondary battery, a battery module or a battery pack according to its usage needs.
[0192] 9 is an example of an electric device, such as a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. A battery pack or a battery module can be used to meet the needs of high power and high energy density for the electric device.
[0193] Another example of the electric device may be a mobile phone, a tablet, a notebook computer, etc. Such an electric device is usually required to be thin and can use a secondary battery as a power source. EXAMPLES
[0194] The following examples are provided to more specifically illustrate the contents disclosed in the present application, and these examples are provided for illustrative purposes only, and various modifications and variations within the scope of the contents disclosed in the present application will be apparent to those skilled in the art. Unless otherwise specified, all parts, percentages and ratios described in the following examples are based on weight, and all reagents used in the examples are commercially available or can be synthesized according to conventional methods and can be used directly without further treatment, and all equipment used in the examples is commercially available.
[0195] Example 1 Preparation of composite graphite materials Petroleum residual oil was subjected to delayed coking treatment at 490℃~510℃ to obtain raw coke, which is a petroleum non-acicular coke. The raw coke was then crushed, molded, and classified to obtain coke powder with a volume average particle diameter Dv50 of 9.5μm, which was used as the main raw material for the composite graphite material.
[0196] Layer distance d 002 Fine expanded graphite (expansion ratio 180) having a particle diameter of 0.3363 nm was pulverized, molded, and classified to obtain fine expanded graphite powder having a volume average particle diameter Dv50 of 7.5 μm.
[0197] Coke powder and fine expanded graphite powder were mixed, and then mixed with coal asphalt as a binder and granulated. The volume average particle diameter Dv50 of the particles obtained by granulation was about 13 μm. The granulated product was placed in a graphite crucible, and the graphite crucible was placed in an Acheson graphitization furnace. Resistance material was filled around the graphite crucible, and electricity was passed through the resistance material to generate heat energy, and the bulk particles were graphitized at about 3000 ° C.
[0198] The obtained bulk particles were mixed with petroleum asphalt, which is an organic carbon source, and then carbonized in a truck kiln at a maximum temperature zone of approximately 1150°C for an operating time of approximately 4 hours in the maximum temperature zone to form a coating layer on at least a portion of the surface of the bulk particles, thereby obtaining a composite graphite material.
[0199] Based on the total mass of the obtained composite graphite material, the mass percent content of the added fine expanded graphite powder was 1%, the mass percent content of the added binder was 6%, and the mass of the added organic carbon source was an amount such that the mass percent content of amorphous carbon obtained by carbonizing the organic carbon source was 3%.
[0200] Manufacture of negative electrode sheets The composite graphite material produced above was used as the negative electrode active material, and the binder styrene butadiene rubber (SBR), thickener sodium carboxymethylcellulose (CMC-Na), and conductive agent carbon black (Super P) were thoroughly mixed in a weight ratio of 96.2:1.8:1.2:0.8 with an appropriate amount of deionized water as a solvent to form a uniform negative electrode slurry. The negative electrode slurry was then evenly applied to the surface of the copper foil as the negative electrode current collector, dried, and cold-rolled to obtain a negative electrode sheet. The negative electrode film layer had an areal density of 0.097 kg / m 2 and the compaction density is 1.64 g / cm 3 It was.
[0201] Manufacture of positive electrode sheets Cathode active material LiNi 0.5 Co 0.2 Mn 0.3O2 (NCM523), conductive carbon nanotubes (CNT), conductive carbon black (Super P), and binder polyvinylidene fluoride (PVDF) were mixed thoroughly in a weight ratio of 97.5:0.5:0.9:1.1 with an appropriate amount of NMP solvent to form a uniform positive electrode slurry, which was then uniformly applied to the surface of the aluminum foil positive electrode current collector, dried, and cold rolled to obtain a positive electrode sheet. The positive electrode membrane layer had an areal density of 0.178 kg / m 2 and the compaction density is 3.4 g / cm 3 It was.
[0202] Separator A porous polyethylene (PE) membrane was used as the separator.
[0203] Electrolyte production Ethylene carbonate (EC), methyl ethyl carbonate (EMC), and diethyl carbonate (DEC) were mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and LiPF6 was uniformly dissolved in the organic solvent to obtain an electrolyte solution, with the concentration of LiPF6 being 1 mol / L.
[0204] Secondary battery manufacturing A positive electrode sheet, a separator, and a negative electrode sheet were stacked in this order and wound up to obtain an electrode assembly. The electrode assembly was then placed in an outer casing, the electrolyte was added, and the secondary battery was obtained through processes such as sealing, standing, chemical formation, and aging.
[0205] Example 2 The preparation method of the secondary battery was similar to that of Example 1, with the difference being that, based on the total mass of the obtained composite graphite material, the mass percent content of the added fine expanded graphite powder was 3%, the mass percent content of the added binder was 6%, and the mass of the added organic carbon source was an amount such that the mass percent content of the amorphous carbon obtained by carbonizing the organic carbon source was 3%.
[0206] Example 3 The method for preparing the secondary battery was similar to that of Example 1, with the difference being that, based on the total mass of the obtained composite graphite material, the mass percent content of the added fine expanded graphite powder was 8%, the mass percent content of the added binder was 6%, and the mass of the added organic carbon source was an amount such that the mass percent content of the amorphous carbon obtained by carbonizing the organic carbon source was 3%,
[0207] Example 4 The preparation method of the secondary battery was similar to that of Example 1, with the difference being that the mass percent content of the added fine expanded graphite powder was 12%, the mass percent content of the added binder was 6%, and the mass of the added organic carbon source was such that the mass percent content of the amorphous carbon obtained by carbonizing the organic carbon source was 3%, based on the total mass of the obtained composite graphite material.
[0208] Example 5 The preparation method of the secondary battery was similar to that of Example 1, with the difference being that the mass percent content of the added fine expanded graphite powder was 20%, the mass percent content of the added binder was 6%, and the mass of the added organic carbon source was an amount such that the mass percent content of the amorphous carbon obtained by carbonizing the organic carbon source was 3%, based on the total mass of the obtained composite graphite material.
[0209] Example 6 The method for preparing the secondary battery was similar to that of Example 1, with the difference being that, based on the total mass of the obtained composite graphite material, the mass percent content of the added fine expanded graphite powder was 30%, the mass percent content of the added binder was 6%, and the mass of the added organic carbon source was an amount such that the mass percent content of the amorphous carbon obtained by carbonizing the organic carbon source was 3%.
[0210] Example 7 The method for preparing the secondary battery was similar to that of Example 3, except that instead of fine expanded graphite powder, the interlayer distance d 002 The hard carbon powder used had a particle diameter of 0.33615 nm and a volume average particle diameter Dv50 of 5.3 μm.
[0211] Example 8 The method for preparing the secondary battery was similar to that of Example 3, except that instead of fine expanded graphite powder, the interlayer distance d 002 The expanded graphite powder (expansion ratio 300) had a mean particle diameter of 0.33638 nm and a volume average particle diameter Dv50 of 7.2 μm.
[0212] Example 9 The method for preparing the secondary battery was similar to that of Example 3, except that instead of fine expanded graphite powder, the interlayer distance d 002 The graphene powder used had a mean particle diameter of 0.33620 nm and a volume average particle diameter Dv50 of 8.0 μm.
[0213] Example 10 The method for preparing the secondary battery was similar to that in Example 1, except that the composite graphite material was prepared as follows.
[0214] Petroleum residual oil was subjected to delayed coking treatment at 490℃~510℃ to obtain raw coke, which is a petroleum non-acicular coke. The obtained raw coke was then crushed, molded, and classified to obtain coke powder with a volume average particle size Dv50 of 9.5μm, which was used as the main raw material for the composite graphite material.
[0215] Layer distance d 002 Fine expanded graphite (expansion ratio 180) having a particle diameter of 0.3363 nm was pulverized, molded, and classified to obtain fine expanded graphite powder having a volume average particle diameter Dv50 of 7.5 μm.
[0216] The coke powder was mixed with coal asphalt as a binder, and granulated. The particles obtained after granulation had a volume average particle diameter Dv50 of about 13 μm. The granulated product was placed in a graphite crucible, and the graphite crucible was placed in an Acheson graphitization furnace. Resistance material was filled around the graphite crucible, and electricity was passed through the resistance material to generate heat energy, and the bulk particles were graphitized at about 3000 °C.
[0217] The obtained bulk particles were mixed with fine expanded graphite powder and petroleum asphalt, which is an organic carbon source, and then carbonized in a truck kiln at a maximum temperature zone of about 1150°C for a maximum temperature zone operation time of about 4 hours to form a coating layer on at least a portion of the surface of the bulk particles, thereby obtaining a composite graphite material.
[0218] Based on the total mass of the obtained composite graphite material, the mass percent content of the added fine expanded graphite powder was 8%, the mass percent content of the added binder was 6%, and the mass of the added organic carbon source was an amount such that the mass percent content of amorphous carbon obtained by carbonizing the organic carbon source was 3%.
[0219] Example 11 The preparation method of the secondary battery was similar to that of Example 1, except that the composite graphite material was prepared as follows:
[0220] Petroleum residual oil was subjected to delayed coking treatment at 490℃~510℃ to obtain raw coke, which is a petroleum non-acicular coke. The obtained raw coke was then crushed, molded, and classified to obtain coke powder with a volume average particle size Dv50 of 9.5μm, which was used as the main raw material for the composite graphite material.
[0221] Layer distance d 002 Fine expanded graphite (expansion ratio 180) having a particle diameter of 0.3363 nm was pulverized, molded, and classified to obtain fine expanded graphite powder having a volume average particle diameter Dv50 of 7.5 μm.
[0222] The coke powder was mixed with fine expanded graphite powder, and then mixed with coal asphalt as a binder, granulated, and the particles obtained after granulation had a volume average particle diameter Dv50 of about 13 μm. The granulated product was placed in a graphite crucible, and the graphite crucible was placed in an Acheson graphitization furnace, and the graphite crucible was filled with resistive material, and electricity was passed through the resistive material to generate heat energy, and the bulk particles were graphitized at about 3000 ° C.
[0223] The obtained bulk particles were mixed with fine expanded graphite powder and petroleum asphalt, which is an organic carbon source, and then carbonized in a truck kiln at a maximum temperature zone of about 1150°C for a maximum temperature zone operation time of about 4 hours to form a coating layer on at least a portion of the surface of the bulk particles, thereby obtaining a composite graphite material.
[0224] Based on the total mass of the obtained composite graphite material, the sum of the mass percent content of the fine expanded graphite powder added in two batches was 10%, the mass percent content of the binder added was 6%, and the mass of the organic carbon source added was an amount such that the mass percent content of the amorphous carbon obtained by carbonizing the organic carbon source was 3%.
[0225] Example 12 The method for preparing the secondary battery was similar to that in Example 3, except that the negative electrode sheet was prepared in the following manner.
[0226] The composite graphite material prepared above was used as the negative electrode active material, and a binder, styrene butadiene rubber (SBR), a thickener, sodium carboxymethyl cellulose (CMC-Na), and a conductive agent, carbon black (Super P), were mixed in a weight ratio of 96.2:1.8:1.2:0.8. The mixture was then mixed with the fine expanded graphite powder in a weight ratio of 96:4. An appropriate amount of deionized water, a solvent, was added, and the mixture was thoroughly stirred and mixed to form a uniform negative electrode slurry. The negative electrode slurry was uniformly applied to the surface of a copper foil, which was a negative electrode current collector, and the mixture was dried and cold-rolled to obtain a negative electrode sheet.
[0227] Example 13 The method for preparing the secondary battery was similar to that of Example 10, except that the negative electrode sheet was prepared in the following manner.
[0228] The composite graphite material prepared above was used as the negative electrode active material, and a binder, styrene butadiene rubber (SBR), a thickener, sodium carboxymethyl cellulose (CMC-Na), and a conductive agent, carbon black (Super P), were mixed in a weight ratio of 96.2:1.8:1.2:0.8. The mixture was then mixed with the fine expanded graphite powder in a weight ratio of 96:4. An appropriate amount of deionized water, a solvent, was added, and the mixture was thoroughly stirred and mixed to form a uniform negative electrode slurry. The negative electrode slurry was uniformly applied to the surface of a copper foil, which was a negative electrode current collector, and the mixture was dried and cold-rolled to obtain a negative electrode sheet.
[0229] Example 14 The method for preparing the secondary battery was similar to that of Example 11, except that the negative electrode sheet was prepared in the following manner.
[0230] The composite graphite material prepared above was used as the negative electrode active material, and a binder, styrene butadiene rubber (SBR), a thickener, sodium carboxymethyl cellulose (CMC-Na), and a conductive agent, carbon black (Super P), were mixed in a weight ratio of 96.2:1.8:1.2:0.8. The mixture was then mixed with the fine expanded graphite powder in a weight ratio of 96:4. An appropriate amount of deionized water as a solvent was added, and the mixture was thoroughly stirred and mixed to form a uniform negative electrode slurry. The negative electrode slurry was uniformly applied to the surface of a copper foil as a negative electrode current collector, and the mixture was dried and cold-rolled to obtain a negative electrode sheet.
[0231] Example 15 The method for preparing the secondary battery was similar to that in Example 1, except that the composite graphite material was prepared in the following manner.
[0232] Petroleum residual oil was subjected to delayed coking treatment at 490℃~510℃ to obtain raw coke, which is a petroleum non-acicular coke. The raw coke was then crushed, molded, and classified to obtain coke powder with a volume average particle diameter Dv50 of 7.0μm, which was used as the main raw material for the composite graphite material.
[0233] Layer distance d 002Fine expanded graphite (expansion ratio 180) having a particle diameter of 0.3363 nm was pulverized, molded, and classified to obtain fine expanded graphite powder having a volume average particle diameter Dv50 of 6.5 μm.
[0234] Coke powder and fine expanded graphite powder were mixed, and then mixed with coal asphalt as a binder and granulated. The volume average particle diameter Dv50 of the particles obtained by granulation was about 9 μm. The granulated product was placed in a graphite crucible, and the graphite crucible was placed in an Acheson graphitization furnace. Resistance material was filled around the graphite crucible, and electricity was passed through the resistance material to generate heat energy, and the bulk particles were graphitized at about 3000 ° C.
[0235] The obtained bulk particles were mixed with petroleum asphalt, which is an organic carbon source, and then carbonized in a truck kiln at a maximum temperature zone of approximately 1150°C for an operating time of approximately 4 hours in the maximum temperature zone to form a coating layer on at least a portion of the surface of the bulk particles, thereby obtaining a composite graphite material.
[0236] Based on the total mass of the obtained composite graphite material, the mass percent content of the added fine expanded graphite powder was 20%, the mass percent content of the added binder was 6%, and the mass of the added organic carbon source was an amount such that the mass percent content of the amorphous carbon obtained by carbonizing the organic carbon source was 3%.
[0237] Example 16 The method for preparing the secondary battery was similar to that in Example 1, except that the composite graphite material was prepared in the following manner.
[0238] Petroleum residual oil was subjected to delayed coking treatment at 490℃~510℃ to obtain raw coke, which is a petroleum non-acicular coke. The raw coke was then crushed, molded, and classified to obtain coke powder with a volume average particle diameter Dv50 of 11.5μm, which was used as the main raw material for the composite graphite material.
[0239] Layer distance d 002Fine expanded graphite (expansion ratio 180) having a particle diameter of 0.3363 nm was pulverized, molded, and classified to obtain fine expanded graphite powder having a volume average particle diameter Dv50 of 7.5 μm.
[0240] Coke powder was mixed with fine expanded graphite powder, and then mixed with coal asphalt as a binder and granulated. The volume average particle diameter Dv50 of the granulated particles was about 14.5 μm. The granulated product was placed in a graphite crucible, and the graphite crucible was placed in an Acheson graphitization furnace. Resistance material was filled around the graphite crucible, and electricity was passed through the resistance material to generate heat energy, and the bulk particles were graphitized at about 3000 ° C.
[0241] The obtained bulk particles were mixed with petroleum asphalt, which is an organic carbon source, and then carbonized in a truck kiln at a maximum temperature zone of approximately 1150°C for an operating time of approximately 4 hours in the maximum temperature zone to form a coating layer on at least a portion of the surface of the bulk particles, thereby obtaining a composite graphite material.
[0242] Based on the total mass of the obtained composite graphite material, the mass percent content of the added fine expanded graphite powder was 1%, the mass percent content of the added binder was 6%, and the mass of the added organic carbon source was an amount such that the mass percent content of the amorphous carbon obtained by carbonizing the organic carbon source was 3%.
[0243] Comparative Example 1 The method for preparing the secondary battery was similar to that of Example 1, except that general-purpose artificial graphite without a coating layer was used as the negative electrode active material. The artificial graphite was prepared by the following method.
[0244] Petroleum residual oil was subjected to delayed coking treatment at 490℃-510℃ to obtain raw coke, which is a petroleum non-acicular coke, and the raw coke was crushed, molded, and classified to obtain coke powder with a volume average particle size Dv50 of 9.5μm.
[0245] The coke powder was mixed with the binder coal asphalt and granulated, and the particles obtained by granulation had a volume average particle size Dv50 of about 13 μm. The granulated product was placed in a graphite crucible, and the graphite crucible was placed in an Acheson graphitization furnace, and a resistive material was filled around the graphite crucible, and electricity was passed through the resistive material to generate heat energy, and the graphitization treatment was performed at about 3000 ° C to obtain artificial graphite. Based on the total mass of the obtained artificial graphite, the mass percent content of the added binder was 6%.
[0246] Comparative Example 2 The method for preparing the secondary battery was similar to that in Example 1, except that the composite graphite material was prepared in the following manner.
[0247] Petroleum residual oil was subjected to delayed coking treatment at 490℃~510℃ to obtain raw coke, which is a petroleum non-acicular coke. The raw coke was then crushed, molded, and classified to obtain coke powder with a volume average particle diameter Dv50 of 9.5μm, which was used as the main raw material for the composite graphite material.
[0248] The coke powder was mixed with coal asphalt as a binder, and granulated. The particles obtained by granulation had a volume average particle diameter Dv50 of about 13 μm. The granulated product was placed in a graphite crucible, and the graphite crucible was placed in an Acheson graphitization furnace. Resistance material was filled around the graphite crucible, and electricity was passed through the resistance material to generate heat energy, and the bulk particles were graphitized at about 3000 ° C. The obtained bulk particles were mixed with petroleum asphalt, which is an organic carbon source, and then carbonized in a truck kiln at a maximum temperature zone of approximately 1150°C for an operating time of approximately 4 hours in the maximum temperature zone to form a coating layer on at least a portion of the surface of the bulk particles, thereby obtaining a composite graphite material.
[0249] Based on the total mass of the obtained composite graphite material, the mass percent content of the added binder was 6%, and the mass of the added organic carbon source was an amount such that the mass percent content of amorphous carbon obtained by carbonizing the organic carbon source was 3%.
[0250] Measuring part The Dv50 and powder compaction density of the negative electrode active material, and the compaction density of the negative electrode film layer were measured by the methods described above in the specification.
[0251] (1) Measurement of the air oxidation temperature T0 of composite graphite materials The measurement was carried out using a German NETZSCH STA 449 F3 simultaneous thermal analyzer. First, 10±0.05mg of composite graphite material sample was weighed and placed in a flat-bottom Al2O3 crucible without closing the lid, and the machine parameters were set as follows: purge gas was air and the gas flow rate was 60mL / min, protective gas was nitrogen gas and the gas flow rate was 20mL / min, heating rate was 5℃ / min, and the measurement temperature range was 35℃~950℃. When the temperature is below 500℃, there is no characteristic peak at this stage, so it can be heated quickly, for example, the heating rate can be set to 10℃ / min.
[0252] After the thermogravimetry was completed, the thermogravimetry curve (TG) and the differential thermogravimetry curve (DTG) of the composite graphite material were obtained, the peak top temperature T1 of the maximum area peak was read from the differential thermogravimetry curve, and the intersection point of two tangents to two points corresponding to 500°C and the T1 temperature on the thermogravimetry curve was determined, and the temperature corresponding to the intersection point on the thermogravimetry curve was the air oxidation temperature T0 of the composite graphite material.
[0253] (2) Gram capacity measurement of composite graphite material A composite graphite material, a conductive agent, carbon black (SuperP), and a binder, polyvinylidene fluoride (PVDF), were uniformly mixed with a solvent, N-methylpyrrolidone (NMP), in a mass ratio of 91.6:1.8:6.6 to prepare a slurry, which was then applied to a copper foil current collector and dried in an oven. A metallic lithium sheet was used as the counter electrode, and a polyethylene (PE) film was used as the separator. Ethylene carbonate (EC), methyl ethyl carbonate (EMC), and diethyl carbonate (DEC) were mixed in a volume ratio of 1:1:1, and LiPF6 was uniformly dissolved in the solution to obtain an electrolyte, with a LiPF6 concentration of 1 mol / L. A CR2430 button cell was assembled in an argon gas protected glove box. The obtained button battery was allowed to stand for 12 hours, then discharged at a constant current of 0.05C to 0.005V at 25°C, allowed to stand for 10 minutes, discharged at a constant current of 50μA to 0.005V again, allowed to stand for 10 minutes, discharged at a constant current of 10μA to 0.005V again, and charged at a constant current of 0.1C to 2V, and the charge capacity was recorded. The ratio of the charge capacity to the mass of the composite graphite material was the gram capacity of the prepared composite graphite material.
[0254] (3) Rapid charging performance measurement of secondary batteries At 25° C., the secondary battery was charged at a constant current of 0.33 C to a charge cut-off voltage of 4.4 V, then charged at a constant voltage of 0.05 C, allowed to stand for 5 min, and discharged at a constant current of 0.33 C to a discharge cut-off voltage of 2.8 V, and the actual capacity was recorded as C0.
[0255] Then, the secondary batteries were charged at constant current in order at 0.5C0, 1C0, 1.5C0, 2C0, 2.5C0, 3C0, 3.5C0, 4C0, and 4.5C0 to a total battery charge cut-off voltage of 4.4V or a negative electrode cut-off potential of 0V (first come, first served basis). After each charge was completed, the secondary batteries were discharged at 1C0 to a total battery discharge cut-off voltage of 2.8V, and then charged at different charge rates of 10%, 20%, 30%……80% SOC (State of Charge). The negative electrode potential corresponding to charging to a negative electrode potential (charge, charged state) was recorded, and the charge rate-negative electrode potential curves at different SOC states were plotted and linearly fitted to obtain the charge rates corresponding to the negative electrode potential of 0 V at different SOC states. The charge rates were the charging windows at the SOC states, and were written as C10% SOC, C20% SOC, C30% SOC, C40% SOC, C50% SOC, C60% SOC, C70% SOC, and C80% SOC, respectively. The charging time T (min) for charging the secondary battery from 10% SOC to 80% SOC was calculated based on the formula (60 / C20% SOC+60 / C30% SOC+60 / C40% SOC+60 / C50% SOC+60 / C60% SOC+60 / C70% SOC+60 / C80% SOC)×10%. The shorter the time, the better the rapid charging performance of the secondary battery.
[0256] (4) Cycle life measurement of secondary batteries At 25°C, the secondary battery was charged at a constant current of 0.33C to a charge cutoff voltage of 4.4V, then charged at a constant voltage of 0.05C, left to stand for 5 minutes, and discharged at a constant current of 0.33C to a discharge cutoff voltage of 2.8V, and the initial capacity was recorded as C0. Then, according to the description in Table 1, charging and discharging at 0.33C were performed, and the discharge capacity Cn of each cycle was recorded until the cycle capacity retention rate (i.e., Cn / C0×100%) reached 80%, and the number of cycles was recorded. The higher the number of cycles, the longer the cycle life of the secondary battery.
[0257] [Table 1]
[0258] (5) Secondary battery low-temperature output performance measurement At 25°C, the secondary battery was charged at a constant current of 0.33C to a charge cut-off voltage of 4.4V, then charged at a constant voltage of 0.05C, left for 5min, and discharged at a constant current of 0.33C to a discharge cut-off voltage of 2.8V, and the initial energy was recorded as P0. The secondary battery was then charged at a constant current of 0.33C to a charge cut-off voltage of 4.4V, then charged at a constant voltage of 0.05C, left for 5min, the thermostat temperature was adjusted to -30°C, left for 3h, and discharged at a constant current of 0.33C to a discharge cut-off voltage of 2.5V, and the energy P1 at this time was recorded. P1 / P0 was the discharge energy retention rate of the secondary battery.
[0259] Table 2 shows the preparation parameters of the composite graphite materials of Examples 1 to 16 and Comparative Examples 1 and 2.
[0260] Table 3 shows the measurement results of Examples 1 to 16 and Comparative Examples 1 and 2.
[0261] [Table 2]
[0262] [Table 3]
[0263] As can be seen from the measurement results in Table 3, when the air oxidation temperature T0 of the composite graphite material is 630°C to 730°C, the secondary battery can have significantly improved fast charging performance and low-temperature output performance under the premise of having a high energy density. In addition, the cycle performance of the secondary battery at a large magnification is also significantly improved.
[0264] Fig. 10 shows the thermogravimetric curves and differential thermogravimetric curves of the composite graphite materials prepared in Example 3 and Comparative Example 2. As can be seen from Fig. 10, the composite graphite material of Example 3 has a relatively low air oxidation temperature T0, and the number of end faces and defects contained in the composite graphite material is moderate, so that the secondary battery can have significantly improved fast charging performance and low temperature output performance under the premise of maintaining a high energy density.
[0265] The composite graphite materials of Comparative Example 1 and Comparative Example 2 both had a relatively high air oxidation temperature T0, the composite graphite materials contained a relatively small number of end faces and defects, and the dynamic performance was relatively poor. The secondary batteries were difficult to use under high-rate charge / discharge conditions, and the low-temperature output performance of the secondary batteries was relatively poor.
[0266] The present application is not limited to the above-mentioned embodiment. The above-mentioned embodiment is merely an example, and any embodiment that has substantially the same configuration as the technical idea and has the same effect within the scope of the technical proposal of the present application is included in the technical scope of the present application. In addition, various modifications that a person skilled in the art can conceive of to the embodiment and other forms constructed by combining some of the components in the embodiment are also included in the scope of the present application, as long as they do not deviate from the gist of the present application.
Claims
1. A composite graphite material comprising bulk particles, which are secondary particles formed by agglomerating two or more primary particles, and a coating layer located on at least a part of a surface of the bulk particles, the bulk particles comprising artificial graphite, and the coating layer comprising amorphous carbon, The air oxidation temperature T 0 is 630°C to 730°C, The air oxidation temperature T 0 The thermogravimetric curve of the composite graphite material is 1 is a temperature corresponding to the intersection of two tangents of two points corresponding to the temperature and the ... 1 The temperature is a peak top temperature of the maximum area peak in a differential thermogravimetry curve of the composite graphite material, and the thermogravimetry curve and the differential thermogravimetry curve are obtained by thermogravimetry performed under conditions of a sample mass of 10±0.05 mg, air as a purge gas, a gas flow rate of 60 mL / min, a heating rate of 5°C / min, and a measurement temperature range of 35°C to 950°C.
2. The composite graphite material further comprises a dynamic carbon material; The dynamic carbon material is located at least in a portion of an interface between primary particles in the bulk particle and / or in the coating layer; 2. The composite graphite material of claim 1, wherein the mass percent content of the dynamic carbon material is 1% to 30%, based on the total mass of the composite graphite material.
3. The composite graphite material according to claim 2, wherein the raw material of the dynamic carbon material is one or more selected from hard carbon, fine expanded graphite, expanded graphite, and graphene, and the interlayer distance d002 of the (002) crystal plane of the dynamic carbon material raw material is 0.3358 nm or more;
4. The interlayer distance d of the (002) crystal plane of the composite graphite material 002 is between 0.3355 nm and 0.3364 nm, and / or The composite graphite material has a volume average particle size Dv50 of 8.5 μm to 14.5 μm, and / or The volume average particle diameter Dv50 of the bulk particles is 7.5 μm to 13.5 μm, and / or The powder compaction density of the composite graphite material at a force of 20,000 N is 1.45 g / cm 3 ~1.75g / cm 3 2. The composite graphite material of claim 1 ,
5. 2. The composite graphite material according to claim 1, wherein the ratio of the volume average particle diameter Dv50 of the primary particles to the volume average particle diameter Dv50 of secondary particles composed thereof is 0.45 to 0.
75.
6. 2. The composite graphite material of claim 1, wherein the mass percent content of amorphous carbon in the coating layer is 1% to 8%, based on the total mass of the composite graphite material.
7. S10: Providing coke powder or coke powder to which a dynamic carbon material raw powder is added, and graphitizing the coke powder or the coke powder to which the dynamic carbon material raw powder is added to obtain bulk particles, the bulk particles being secondary particles formed by agglomeration of two or more primary particles, and the bulk particles including artificial graphite; and S20: Mixing the bulk particles with an organic carbon source, or mixing the bulk particles with an organic carbon source and the dynamic carbon material raw material powder, and forming a coating layer containing amorphous carbon on at least a part of the surface of the bulk particles after carbonization treatment to obtain the composite graphite material; 1. A method for preparing a composite graphite material comprising: The dynamic carbon material raw material powder is added in at least one of steps S10 and S20, and the dynamic carbon material raw material is one or more selected from hard carbon, fine expanded graphite, expanded graphite, and graphene, and the interlayer distance d of the dynamic carbon material raw material (002) crystal plane is 002 ≧0.3358 nm, The air oxidation temperature T of the obtained composite graphite material 0 is 630°C to 730°C, and the air oxidation temperature T 0 The thermogravimetric curve of the composite graphite material is 1 is a temperature corresponding to the intersection of two tangents of two points corresponding to the temperature, 1 the temperature is the peak-top temperature of the maximum area peak in a differential thermogravimetry curve of the composite graphite material, and the thermogravimetry curve and the differential thermogravimetry curve are obtained by thermogravimetry performed under conditions of a sample mass of 10±0.05 mg, air as a purge gas, a gas flow rate of 60 mL / min, a heating rate of 5°C / min, and a measurement temperature range of 35°C to 950°C.
8. The method according to claim 7, wherein based on the total mass of the obtained composite graphite material, the total mass percentage content of the dynamic carbon material raw material powder added in steps S10, S20 is 1%-30%.
9. The volume average particle diameter Dv50 of the coke powder is 6 μm to 12 μm, and / or The volume average particle diameter Dv50 of the dynamic carbon material raw material powder is 3 μm to 12 μm; 8. The method according to claim 7, wherein the ratio of the volume average particle diameter Dv50 of the coke powder to the volume average particle diameter Dv50 of the dynamic carbon material raw powder is 1.05 to 1.
75.
10. Further, the method includes the steps of adding a binder to S10, mixing the binder with coke powder, granulating, and further graphitizing to obtain bulk particles, or mixing the binder with coke powder to which the dynamic carbon material raw material powder is added, granulating, and further graphitizing to obtain bulk particles, Based on the total mass of the resulting composite graphite material, the binder mass percent content is 3% to 12%; The binder is selected from asphalt; The method according to claim 7, wherein the particles obtained by granulation have a volume average particle diameter Dv50 of 8 μm to 14 μm.
11. In S20, the organic carbon source is one or more selected from coal asphalt, petroleum asphalt, phenolic resin, and coconut shell; 8. The method according to claim 7, wherein the amount of the organic carbon source added is such that the mass percent content of amorphous carbon obtained by carbonizing the organic carbon source is 1% to 8%, based on the total mass of the obtained composite graphite material.
12. A negative electrode sheet including a negative electrode current collector and a negative electrode film layer provided on at least one surface of the negative electrode current collector, the negative electrode film layer including the composite graphite material according to any one of claims 1 to 6, The negative electrode film layer further contains an additive, the additive being one or more selected from hard carbon, fine expanded graphite, expanded graphite, and graphene, and the interlayer distance d of the additive (002) crystal plane is 002 ≧0.3358 nm, The negative electrode sheet, wherein the mass percentage content of the additive is 1% to 20%, based on the total mass of the negative electrode membrane layer.
13. A secondary battery comprising the negative electrode sheet according to claim 12.
14. A battery module comprising the secondary battery according to claim 13.
15. A battery pack comprising one of the secondary battery according to claim 13 and the battery module according to claim 14.
16. An electric device comprising at least one of the secondary battery according to claim 13, the battery module according to claim 14, and the battery pack according to claim 15.
Citation Information
Patent Citations
Negative electrode material and preparation method thereof, negative plate and lithium ion battery
CN111620332A
Secondary battery and manufacturing method for negative electrode material of carbon
JP2001332263A
Negative electrode active material for lithium secondary battery, method of preparing the same, and negative electrode for lithium secondary battery and lithium secondary battery including the same
US20210126248A1
Artificial graphite, secondary battery, preparation method, and device
WO2021108982A1